Enhancements to the USGS Landsat Level 2 surface temperature and emissivity product for Collection 3 reprocessing - Saeed Arab; Chase Mueller; Christopher J. Crawford; Danika Wellington; Ray Dittmeier; Glynn Hulley; Aaron Gerace; Calli Jenkerson; Simon Hook; Amirhossein Hassanzadeh; Rehman Eon; Cody Anderson; et al. (Remote Sensing of Environment, 2026)

Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Intact coastal nursery rearing amid climate‐driven phenological shifts in threatened salmon - Stuart H. Munsch; Joseph H. Anderson; Eric M. Beamer; Joshua W. Chamberlin; Christopher Ellings; Correigh M. Greene; Sayre Hodgson; Michael T. LeMoine; W. Todd Zackey (Conservation Biology, 2026)
Literature linking phenology to climate has proliferated in recent decades and shows that climate change has reorganized seasonal opportunities worldwide. However, this literature often quantifies changes in point measures of timing (e.g., beginnings and peaks) without context about duration (e.g., rearing season length) or performance (e.g., juvenile development). Consequently, phenological studies often cannot discern whether climate change truncates biological processes or merely recenters them intact around different dates, which limits the utility of these studies for climate vulnerability assessments. Showing how research may bridge this gap, we quantified links between temperature and coastal nursery rearing phenology in threatened Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792). Long nursery rearing periods are crucial to enabling growth that promotes survival and life‐history diversity that spreads risk. Because salmon can express diverse, climate‐influenced phenologies and our study region warmed but remained temperate, we sought to discern whether nursery rearing was intact or truncated amid potential phenological change. Leveraging ∼170,000 observations across three decades and three basins, we found that warm years generally advanced populations’ seasonal trajectories of habitat use and growth and that they did not reduce annual 95th percentile body lengths. Additionally, warm years did not consistently compress or expand habitat use in rivers or deltas but consistently expanded habitat use in nearshore marine waters. Overall, there was substantial evidence that warm years advanced nursery rearing intact and little evidence of truncation. Thus, climate change shifted when populations reared but did not prevent populations from completing rearing. Global research on phenological change has begun to transcend descriptions of patterns to consider biological consequences. Simultaneously, efforts to assess populations’ climate vulnerabilities have become widespread. Studies that inspect phenological change to distinguish intact processes from truncated processes could provide insights into climate vulnerabilities. Coastal nursery rearing is one process that may especially befit this framework.

Oceanographic and climatic controls of meteoric 10Be fluxes to seafloor sediments: A global synthesis - Jennifer Middleton; Frank Pavia; Robert Anderson; Roseanne Schwartz; Martin Fleisher; Yong Lao; Yuxin Zhou; Christopher Kinsley; Joerg Schaefer; Martin Frank; Gisela Winckler (Quaternary Science Reviews, 2026)

WIC Households’ Participation in Multiple Nutrition Assistance Programs and Household Food Insecurity During the COVID-19 Pandemic - M.Pia Chaparro; Shannon E. Whaley; Christopher E. Anderson (Journal of Nutrition Education and Behavior, 2026)

Forest Carbon Diligence: Digital MRV for mapping forest structure and carbon stocks - Christopher B. Anderson; Maxwell B. Joseph; Camile Söthe; Flávia de Souza Mendes; Thomas Maschler; Ryan C. McCarthy; Joseph Mascaro; Tara O’Shea; Amy Rosenthal; David C. Marvin (Forest Ecology and Management, 2026)

Evaluation of the retention process of bile acids by cell surface of inactivated Lacticaseibacillus rhamnosus GG using spray drying under in vitro digestion simulation - Douglas Xavier-Santos; Rodrigo Dias Requião; Paulo César Martins Alves; Christopher Schmidt; Thomas Kurth; Adriane Elisabete Costa Antunes; Stephanie Bader-Mittermaier; Peter Eisner; Anderson S. Sant’Ana (Food Bioscience, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Environmental thresholds and forest vegetation across a tidal gradient of the Mobile-Tensaw River Delta, USA - Andrew Balder; Thomas Kavoo; Christopher J. Anderson; Latif Kalin (Estuarine, Coastal and Shelf Science, 2026)

Response of greenhouse gas emissions, nitrogen loss and microbial communities to the presence of conventional and biodegradable microplastics in soil - Wenxu Li; Mengxiao Li; Jiaju He; Zhenyu Huang; Jian Zeng; Christopher W.N. Anderson; Minghua Zhou; Cheng Zhang; Xuesong Gao; Di Zhao; Ting Lan (Applied Soil Ecology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Placing social imaginaries to reconceptualize conservation from a social-ecological perspective: insights from guided visits to a Patagonian national park - Jessica Balling; Christopher B. Anderson (Journal of Environmental Studies and Sciences, 2026)
More inclusive conservation approaches are needed to achieve the dual goals of justice and sustainability. This imperative requires developing new strategies to adapt extant models like conservation-based tourism in protected areas to incorporate more plural perspectives. We studied guided tours in Tierra del Fuego National Park, Argentina to assess how nature and people-nature relationships were (re)produced. Specifically, we used ethnographic methods (participant observations, interviews, document/media analyses) with the bricolage analytical concept of ‘placing social imaginaries’ to evaluate the ways that materialities, practices, meanings, and institutions interact in the visitation experience. We delimited three dynamic areas of tension evident in the data: (i) remoteness - connectivity, (ii) modernity - postmodernity, and (iii) singular nature - plural people-nature relationships. By analyzing how multiple social imaginaries converge and reproduce different people-nature relationships in touristic experiences, we obtained insights into how a ‘natural’ protected area is conceived, valued, and co-constructed as a dynamic social-ecological system in a specific space-time (i.e. place). We argue that being more intentional and reflexive about the ‘placing of social imaginaries’ can foster more inclusive approaches to conservation-based tourism.

Trophic ecology of the endangered southern river otter (Lontra provocax) in the Fuegian Archipelago, Argentina: knowledge and implications for conservation - Alfredo Ñ. Claverie; Luciana Riccialdelli; Guillermina Massaccesi; Nora Jara; Christopher B. Anderson; Alejandro E. J. Valenzuela (Mammalian Biology, 2026)

Soil and ruminant gut microbiomes in diverse pasture systems and regenerative agriculture: a review - Upulika Jayaneththi; Paramsothy Jeyakumar; Nicholas W. Sneddon; Lucy L. Burkitt; Christopher W. N. Anderson; Lisanne M. Fermin; Daniel J. Donaghy (Biology and Fertility of Soils, 2026)
Pasture systems strongly influence microbiome diversity in both soils and grazing ruminants, and their interactions through interconnected microbial exchange pathways. In temperate regions, grazed pasture systems are predominantly composed of perennial ryegrass-white clover, representing standard systems under contemporary management. However, sustainable alternatives such as regenerative agriculture, which emphasise diverse pasture species, are gaining attention. Diverse pastures, due to their varied root structures and nutritional composition, exert more pronounced effects on soil and ruminant microbiomes than standard swards. This review synthesises current knowledge on soil and ruminant gut microbiome responses to diverse pasture systems. Diverse swards enhance soil organic carbon and microbial abundance, while their varied nutrient profiles and bioactive compounds, together with ingested soil microbes during grazing, contribute to a more diverse and stable gut microbiome, potentially strengthening soil–gut microbial interactions. However, few omics-based studies have explored microbiome responses to pasture management, and none have simultaneously investigated soil and ruminant gut microbiomes under regenerative management. This review highlights these gaps and proposes future research directions, including integrated multi-omics approaches, to advance understanding of soil–gut microbiome dynamics, interactions, and functional roles within pasture-based agroecosystems.

Turbidity and streamflow as real-time indicators of microbial risk for aquatic recreators - Elliot S. Anderson; Christopher S. Jones; Claire E. Hruby (Environmental Monitoring and Assessment, 2026)
Aquatic recreation is a popular pastime, but recreators often incur the risk of acquiring illnesses through exposure to waterborne pathogens. Several standards advise stakeholders on a waterbody’s recreational suitability using indicator bacteria concentrations. However, quantifying indicator organisms often takes several hours or days, resulting in a lack of real-time information. Microbe concentrations can also fluctuate dramatically over short timeframes, making it difficult to systematically assess and communicate risk using discrete samples. This study investigated turbidity and streamflow as real-time predictors of Escherichia coli ( E. coli ) in two major Iowa waterways (the Des Moines and Raccoon Rivers). A large historical dataset ( n > 4000 at both sites) was leveraged to construct logistic models that predicted the probability of E. coli exceeding two recreational water quality standards (235 and 2880 organisms/100 mL). High-resolution turbidity measurements were collected to implement these models and comprehensively estimate long-term exceedance levels of the standards. Models were created at each site that used turbidity as the sole predictor—streamflow proved unnecessary. While these models were viable, their performance was relatively weak (pseudo R 2 between 0.19 and 0.38, sensitivities between 6.8 and 68%), suggesting that turbidity and streamflow alone are likely insufficient for producing real-time predictions of risk at accuracy levels acceptable to stakeholders. Still, there may be utility in deploying similar models to describe a waterway’s propensity to exceed E. coli thresholds over the course of several months or years and to prioritize improvement efforts.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Multi-satellite data fusion for improved field-scale evapotranspiration mapping on Google Earth Engine - Hui Liu; Yun Yang; Martha C. Anderson; Feng Gao; Christopher R. Hain; Vikalp Mishra; John M. Volk; Yanghui Kang (Remote Sensing of Environment, 2026)

Clinical Characteristics and Outcomes of Invasive Aspergillosis in Patients with Hematological Malignancies and Transplantation and Cellular Therapies in the Contemporary Era - Christopher M. Lopez; Jose F. Suarez; Maria A. Mendoza; Anthony D. Anderson; Jill Lykon; Wenhui Li; Michele I. Morris; Yoichiro Natori; Mohammed Raja; Lazaros J. Lekakis; Amer Beitinjaneh; Antonio Jimenez; et al. (Mycopathologia, 2026)
Background Despite important advancements in diagnostic modalities, routine use of therapeutic drug monitoring (TDM) and newer antifungal therapies, there is a paucity of contemporary data regarding clinical characteristics and outcomes of invasive aspergillosis (IA) in the United States. Methods Single-center, retrospective cohort study of hospitalized patients between 2015 and 2020, who had active hematological malignancy (HM) or had undergone transplantation and cellular therapy (TCT) and had probable or proven IA. Results Sixty-two patients with probable or proven IA, including 21 HM and 41 TCT, were identified. Forty-four percent of the cases corresponded to breakthrough IA. Bronchoalveolar lavage galactomannan was ≥ 1 in 71% and ≥ 0.5 in 88%, while serum galactomannan was ≥ 0.5 in only 34%. Among assessable patients (n = 59), 90-day partial or complete response to antifungal therapy occurred in 39%. All-cause mortality for the entire cohort was 22% at 30 days and 46% at 90 days. IA attributable mortality was 18% at 30 days and 38% at 90 days. Achieving therapeutic antifungal serum levels was associated with a reduction in all-cause mortality, while prior clinically significant CMV infection (aOR 9.65, 95% CI 1.34–69.6; P = 0.025) and relapsed/refractory hematological disease (aOR 8.5, 95% CI 2.23, 32.4; P = 0.002) were associated with higher IA attributable mortality. Conclusions Despite advancements in diagnosis and treatment, IA remains associated with poor outcomes in hematological patients in the contemporary era. Newer antifungals and improved strategies for monitoring and prevention of IA in these vulnerable patient populations are urgently needed.

Earthworm assemblages in the Eastern and Midwestern United States and the legacy of glaciation - Timothy S. McCay; Laurel J. Anderson; Christopher P. Bloch; Abigail E. Cahill; Sandra L. Cooke; Benjamin J. Dolan; Kathryn M. Flinn; Danielle Garneau; Nathaniel J. Hains; Kristy Hopfensperger; Mary Beth Kolozsvary; Carol Mankiewicz; et al. (Biological Invasions, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Carbon capture from ArcelorMittal hot briquetted Iron plant using air liquide cryocap™ FG technology – FEED study - Sebastiano Giardinella; Varun Gopalakrishnan; Vincent Gueret; Lindsey Turney; Vincent Lu; Chris Tovee; David Zybko; Marcelo Andrade; Christopher Harris; Pierre-Philippe Guerif; Timothy Henderson; Anderson Morelato; et al. (International Journal of Greenhouse Gas Control, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Participation in multiple nutrition assistance programs early in the COVID-19 pandemic and dietary intake frequencies among WIC-participating children ages 1–4 years - M. Pia Chaparro; Shannon E. Whaley; Christopher E. Anderson (Appetite, 2026)

Navigating diverse human–nature worldviews for more inclusive conservation - Ranjini Murali; Christopher B. Anderson; Barbara Muraca; Paola Arias‐Arévalo; Rachelle K. Gould; Dominic Lenzi; Eglee Zent; Simone Athayde; Jasper Kenter; Christopher M. Raymond; Arild Vatn (Conservation Biology, 2026)
D ifferent worldviews shape how humans perceive, understand, inhabit, and value the world. Major efforts to achieve more inclusive conservation, such as the Kunming–Montreal Global Biodiversity Framework, seek to more fully reflect diverse worldviews in science, policy, and practice. Building on the Intergovernmental Platform on Biodiversity and Ecosystem Services Values Assessment ’s comprehensive review of academic publications, Indigenous and local knowledge sources, and policy documents, we characterize 4 human–nature worldviews: anthropocentrism, biocentrism, ecocentrism, and pluricentrism. This heuristic typology can help conservation scholars and practitioners navigate participatory decision‐making by providing conceptual clarity to distinguish particular worldviews and the fuzzy boundaries between them, and by addressing practical issues, particularly discursive and structural power dynamics, that affect worldview expression. Two case studies, protected area prioritization in India and payments for ecosystem services in Colombia, show that inclusive conservation depends on strategies and abilities to recognize and understand diverse worldviews and to articulate them in institutions. These examples highlight that engaging diverse human–nature worldviews applies not only to developing new policies but also to adapting mainstream instruments.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Real-Time Acoustic Telemetry Buoys as Tools for Nearshore Monitoring and Management - James M. Anderson; Brian S. Stirling; Patrick T. Rex; Emily A. Spurgeon; Anthony McGinnis; Zachariah S. Merson; Darnell Gadberry; Christopher G. Lowe (Journal of Marine Science and Engineering, 2026)
Acoustic telemetry monitoring for tagged sharks in nearshore waters has become an important tool for beach safety management; however, detection performance can vary widely in shallow, high-energy nearshore environments where management decisions are often most time-sensitive. Real-time acoustic telemetry buoys offer the potential to deliver live detections and system diagnostics, but their performance relative to autonomous bottom-mounted receivers remains poorly evaluated under realistic coastal conditions. We compared the detection efficiency of real-time buoy-mounted acoustic receivers and autonomous bottom-mounted receivers across five nearshore sites in southern California. Using paired long-term reference tag deployments and short-term range tests, we quantified detection probability, effective detection range, and the influence of environmental conditions and receiver placement. Detection performance was evaluated in relation to wind speed, water temperature, receiver tilt, and signal-to-noise ratio. Both buoy-mounted and bottom-mounted receivers maintained high long-term detection efficiency, recovering 77–99% of expected transmissions at 82–250 m. Range tests indicated greater effective detection distances for buoy-mounted receivers, with 50% detection probabilities occurring at approximately 471 m compared to 282 m for bottom-mounted receivers. Receiver placement strongly influenced performance, with surface-mounted receivers outperforming bottom-mounted units regardless of receiver model. Environmental effects on detections were site-specific and variable. Detection probability varied predictably with environmental conditions. Higher SNR increased detection success, particularly for bottom/substrate mounted receivers, while warm water significantly reduced detection probability across placement configuration. These results demonstrate that real-time acoustic telemetry buoys provide reliable detection performance in dynamic nearshore environments while offering key operational advantages, including immediate data access and system diagnostics. The observed relationships demonstrate that receiver performance is dynamic rather than fixed, and that real-time buoy systems therefore represent a practical tool for coastal monitoring programs that require timely information to support adaptive management, public safety, and conservation decision making.

Corrigendum to “Tourist preferences for whale watching and rule changes in the Salish Sea” [Ocean Coast. Manag. 269 (2025) 107830] - Abby Schamp; Hem Nalini Morzaria-Luna; Melissa Knox; Christopher M. Anderson (Ocean & Coastal Management, 2026)

A review of the cast stone formulation for nuclear waste immobilization - R. Matthew Asmussen; Gemma G. Clark; Jacob Anderson; Agathe Bourchy; Jacqueline Ferrer; Christopher Hossack; Jonathan Lapeyre; Miroslava Peterson; Suraj A. Rahmon; Joelle T. Reiser; Brian J. Riley; Sarah A. Saslow; et al. (Waste Management, 2026)

Intercomparison of Earth Observation products for hyper-resolution hydrological modelling over Europe - Almudena García-García; Pietro Stradiotti; Federico Di Paolo; Paolo Filippucci; Milan Fischer; Matěj Orság; Luca Brocca; Jian Peng; Wouter Dorigo; Alexander Gruber; Bram Droppers; Niko Wanders; et al. (Remote Sensing of Environment, 2026)

Comparative analysis of the photosynthetic ecophysiology of Myriophyllum aquaticum and congeneric milfoils and invasion potential into the Midwestern United States - Alyssa J. Anderson; Ryan M. Wersal; Christopher T. Ruhland (Aquatic Botany, 2026)

Correction: Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)

Controlling harmful algal blooms (HABs) in marine waters: Review of current status and future prospects - Donald M. Anderson; Mark L. Wells; Vera L. Trainer; Marc Suddleson; Kevin Claridge; Kathryn J. Coyne; Quay Dortch; Christopher J. Gobler; Cynthia A. Heil; Nobuharu Inaba; H. Dail Laughinghouse; Jorge I. Mardones; et al. (Harmful Algae, 2025)

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)
Introduction Species distribution models (SDMs) are increasingly used in fisheries science to understand species’ spatial patterns and improve stock assessments. Method This study developed SDMs for eulachon smelt ( Thaleichthys pacificus ), a threatened, demersal forage fish often caught as bycatch in the United States West Coast ocean shrimp trawl fishery. Using ten years of observer data (2012–2021, n=19,749 with 25.4% being zeros), the study assessed the influence of static (e.g., substrate) and dynamic (e.g., ocean temperature, currents) environmental variables on eulachon abundance. Results The best-performing SDM included near-bottom temperature and current data, outperforming SDMs using only surface variables. Eulachon abundance peaked at ~150 m depth, especially over gravel substrates, and during nighttime. Although none of the SDM-based abundance indices significantly correlated with the Columbia River stock assessment index, bottom-based SDMs showed stronger alignment with the stock assessment (R=0.61, p=0.08 & R=0.62, p=0.07). Discussion Management implications are significant. Rock habitats were associated with higher eulachon bycatch, and vessels can use bottom-typing tools to avoid them. Also, delaying the season opener could reduce bycatch, as eulachon catch was reduced by 0.0109 mt per trawl over the interquartile range of day of the year. These findings can inform Best Management Practices (BMPs), which have historically led to regulatory changes such as the adoption of excluder grates and LED lights. Overall, incorporating near-bottom oceanographic data greatly enhanced predictive performance, especially for demersal species like eulachon. These mechanistic SDMs can be projected forward, aiding future management amid changing ocean conditions. While some discrepancies remain, this approach offers promising insights for adaptive fishery management and conservation of imperiled species like eulachon.

Synergistic use of ICESat-2 lidar data and Sentinel-2 imagery for assessing hurricane-driven forest changes - Ajay Gautam; Lana L. Narine; Christopher J. Anderson; Richard Cristan (Environmental Monitoring and Assessment, 2025)
Coastal forests worldwide are vulnerable to hurricanes, which cause significant canopy loss and long-term disruption of ecosystem services. Scalable methods for assessing hurricane-driven forest damage are critical for ecosystem recovery, yet conventional field-based approaches are time-consuming, costly and challenging to acquire over large areas. The Ice Cloud and land Elevation Satellite-2 land and vegetation height product (ATL08) provides three-dimensional information, and its capability of measuring forest structure is already well demonstrated. However, its integration with satellite imagery for mapping hurricane-induced canopy height changes remains limited. In this study, we analyzed coastal forest canopy losses and thematic transitions using ICESat-2, Sentinel-2, and ancillary predictors. We used Random Forest (RF) and Extreme Gradient Boosted (XGB) regression models to extrapolate ATL08 pre-hurricane canopy heights and applied the better-performing model for post-hurricane mapping. The resulting canopy height maps were combined with existing land cover products to assess structural and thematic transitions across the impacted landscape. RF outperformed XGB (R 2 = 0.44, RMSE = 4.30 m vs. R 2 = 0.41, RMSE = 4.76 m). Landcover shifts included transitions from evergreen to herbaceous, scrub, and barren classes, and from woody wetlands to emergent herbaceous wetlands, with mean canopy height losses of 2.3–5.2 m. Canopy cover analysis showed dense (> 60%) and sparse (< 30%) cover experienced greatest losses (up to 8.3 m), while moderate covers (30–60%) were resilient. This study demonstrates the potential of integrating ICESat-2 and Sentinel-2 for assessing structural and thematic changes and informing adaptive strategies in hurricane-prone coastal ecosystems.

Tourist preferences for whale watching and rule changes in the Salish Sea - Abby Schamp; Hem Nalini Morzaria-Luna; Melissa Knox; Christopher M. Anderson (Ocean & Coastal Management, 2025)

Household WIC Benefit Redemption Varies by Participant and Household Characteristics in Southern California - Christopher E. Anderson; Shannon E. Whaley (Journal of the Academy of Nutrition and Dietetics, 2025)

Wildlife of tidal forested wetlands in the southeastern Atlantic United States - James T. Anderson; Andrew P. Hopkins; Crystal Anderson; Miriam Boucher; Rene Brown; Aruã de Castro; Sindupa De Silva; Robert M. Greco; Jordan E. McCall; Oluwatobi Emmanuel Olaniyi; Christopher Pettengill; Akshit R. Suthar; et al. (Estuarine, Coastal and Shelf Science, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

WIC Service Use, Benefit Redemption, and Continued Participation Among Participants in California - Christopher E. Anderson; Catherine E. Yepez; Shannon E. Whaley (Journal of the Academy of Nutrition and Dietetics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Salinity Variability in Tidal Creeks and the Role of Watershed Development - Sam Bickley; Christopher J. Anderson (Estuaries and Coasts, 2025)
Salinity variability across estuaries is attributed to patterns of freshwater inflow, and there is increasing awareness of the effect it can have on the ecological function of estuaries. In addition to natural causes related to climate and proximity to freshwater sources, there are anthropogenic factors that may increase salinity variability. One less considered urban impact on estuaries is the potential for increased stormwater runoff and water yield to tidal creeks which may artificially shift salinity regimes. To better understand natural and anthropogenic causes of salinity variation, we installed conductivity sensors and data loggers near the outlet of 12 s- and third-order, mesohaline tidal creeks across an urban gradient in Alabama and west Florida, USA. Like many coastal zones, this area is currently experiencing rapid urban development characterized by the spread of low- to moderate-density suburban and commercial land use. Conductivity and temperature data were logged in each creek every 15 min and used to generate a time series of daily mean and 1-h mean salinity (ppt) between June 2019 and May 2020. Using 1-h mean salinity data, variability was calculated from time series and compared using three different measures: mean salinity timestep Δ (MSTΔ), mean daily salinity range (MDSR), and salinity variance. We found that proximity to major river outlets strongly affected three of the monitored creeks and was an overriding factor in both mean daily salinity and salinity variability. The other creeks less affected by nearby rivers were more comparable, and data showed that all three measures of salinity variability had positive relationships with watershed urban land use. Salinity variation changed markedly with seasons, but the positive relationship between watershed urban land use and salinity variability was consistent. Our results suggest that urbanization, even at low- to moderate levels, can lead to detectable shifts in salinity patterns. Because climate change is leading to both more intense storms and rising sea levels, further research is needed to understand how these changes may interact with continued coastal development to affect the ecological functioning of estuaries.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

A Review of Global Fisheries Performance - Frank Asche; Taryn M. Garlock; James L. Anderson; Ruth B. Pincinato; Christopher M. Anderson; Edward V. Camp; Jingjie Chu; Andreea L. Cojocaru; Hakan Eggert; Kai Lorenzen; David C. Love; Ragnar Tveteras (Fish and Fisheries, 2025)
Management of fisheries is complex as it combines environmental, economic and social objectives. The relative importance of these objectives is highly debated and the best approaches to achieving good outcomes are unclear. A lack of global and multi‐dimensional data has largely precluded reviews providing comparisons of performances across systems at a large scale. We review fisheries performance by analysing outcomes over 14 dimensions of environmental, economic and community performance using a unique global dataset for 145 fisheries collected with the Fishery Performance Indicators. The fisheries are ranked into three performance groups by an average of their environmental, economic and community scores: the 10% best fisheries, the 10% worst fisheries and the middle 80%. Furthermore, we investigate how four different types of management systems, catch shares, territorial use rights, limited entry and open access, are represented in the three performance groups. The best performing fisheries scored equally or better and the poorest performing fisheries scored equally or worse in environmental, economic and social dimensions. We found three different management systems to be represented among the best performing fisheries, indicating that no specific management system is best. Moreover, some management systems were represented in all three performance categories, indicating that fisheries characteristics or management designs are important elements of fishery performance. The worst performing fisheries were dominated by open access fisheries with no or very limited management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Agroecosystem’s contributions to people: how ranchers and specialists perceive threatened Espinal forests used for cattle-grazing - Ignacio J. Rojido; Christopher B. Anderson; Marina Tagliaferro; Sonia B. Canavelli (Environmental Management, 2025)

tinyVAST : R Package With an Expressive Interface to Specify Lagged and Simultaneous Effects in Multivariate Spatio‐Temporal Models - James T. Thorson; Sean C. Anderson; Pamela Goddard; Christopher N. Rooper (Global Ecology and Biogeography, 2025)
Aim Multivariate spatio‐temporal models are widely applicable, but specifying their structure is complicated and may inhibit wider use. We introduce the R package tinyVAST from two viewpoints: the software user and the statistician. Innovation From the user viewpoint, tinyVAST adapts a widely used formula interface to specify generalised additive models and combines this with arguments to specify spatial and spatio‐temporal interactions among variables. These interactions are specified using arrow notation (from structural equation models) or an extended arrow‐and‐lag notation that allows simultaneous, lagged and recursive dependencies among variables over time. The user also specifies a spatial domain for areal (gridded), continuous (point‐count) or stream‐network data. From the statistician viewpoint, tinyVAST constructs sparse precision matrices representing multivariate spatio‐temporal variation, and parameters are estimated by specifying a generalised linear mixed model (GLMM). This expressive interface encompasses vector autoregressive, empirical orthogonal functions, spatial factor analysis and ARIMA models. Main Conclusion To demonstrate, we fit to data from two survey platforms sampling corals, sponges, rockfishes and flatfishes in the Gulf of Alaska and Aleutian Islands. We then compare eight alternative model structures using different assumptions about habitat drivers and survey detectability. Model selection suggests that towed‐camera and bottom trawl gears have spatial variation in detectability but sample the same underlying density of flatfishes and rockfishes and that rockfishes are positively associated with sponges while flatfishes are negatively associated with corals. We conclude that tinyVAST can be used to test complicated dependencies representing alternative structural hypotheses for research and real‐world policy evaluation.

Cervical cancer screening rates in females living with HIV at three healthcare settings in the United States, 2010–2019 - Leigh Sheridan; Gaia Pocobelli; Melissa Anderson; Christopher I. Li; Gina R. Kruse; Jasmin A. Tiro; Aruna Kamineni (Cancer Causes & Control, 2025)

Strain rates recorded in the perimeter-area relationship of recrystallized quartz aggregates from the Sandhill Corner shear zone, Maine, USA - Erik K. Anderson; Won Joon Song; Scott E. Johnson; Christopher C. Gerbi (Journal of Structural Geology, 2025)

In situ Rb–Sr geochronology of slickensides reveals reactivation of cratonic margins post-Gondwana assembly - Ingridy S. Nicomedes; Bruno V. Ribeiro; Fabricio A. Caxito; Christopher L. Kirkland; Anderson Victoria; Zakaria Quadir (Journal of Structural Geology, 2025)

eDNA metabarcoding detection of nearshore juvenile white sharks (Carcharodon carcharias) and prey fish communities - Zachariah S. Merson; Elizabeth E. Jahn; Matthew A. Barnes; Emily A. Spurgeon; Patrick T. Rex; Jack T. Elstner; Yamilla N. Samara Chacon; James M. Anderson; Whitney D. Jones; Christopher G. Lowe (Journal of Experimental Marine Biology and Ecology, 2025)

COP16 and the process of consolidating an inclusive conservation paradigm - Christopher B. Anderson (Conservation Biology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Tetracycline resistance gene transfer from Escherichia coli donors to Salmonella Heidelberg in chickens is impacted by the genetic context of donors - Vanina Guernier-Cambert; Julian Trachsel; Briony Atkinson; Adelumola Oladeinde; Christopher L. Anderson; Shawn M.D. Bearson; Melissa S. Monson; Torey Looft (Veterinary Microbiology, 2024)

Using mercury and lead stable isotopes to assess mercury, lead, and trace metal source contributions to Great Salt Lake, Utah, USA - Samuel F. Lopez; Sarah E. Janssen; Michael T. Tate; Diego P. Fernandez; Christopher R. Anderson; Grace J. Armstrong; Thomas C. Wang; William P. Johnson (Science of The Total Environment, 2024)

Interactive effects of microplastics and cadmium on soil properties, microbial communities and bok choy growth - Mengxiao Li; Jiaju He; Xiaofeng Chen; Xiaoman Dong; Shuang Liu; Christopher W.N. Anderson; Minghua Zhou; Xuesong Gao; Xiaoyan Tang; Di Zhao; Ting Lan (Science of The Total Environment, 2024)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Social perceptions regarding rivers associated with the sugar industry in Tucumán, Argentina - Paola Alberti; Juan Cruz Gonzalez; Eduardo Domínguez; Christopher B. Anderson (Regional Environmental Change, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Grazers and predators mediate the post-settlement bottleneck in Caribbean octocoral forests - Christopher D. Wells; Joseph Benz; Kaitlyn J. Tonra; Emily R. Anderson; Howard R. Lasker (Frontiers in Marine Science, 2024)
In the Caribbean, reef-building scleractinian corals have declined precipitously and octocorals have emerged as one of their main successors. The success of octocorals and the formation of octocoral forests has been attributed to their continuing recruitment to reef habitats, as well as tolerance to pollution, reduced direct competition with scleractinians, and resistance and resilience to climatic events. Benthic grazers on coral reefs can facilitate the growth and recruitment of corals by reducing the abundance of competitive algal turfs and macroalgae. However, grazing can also hinder corals through sublethal damage to coral tissue and predation of recruits. We assessed the effects of grazing by fishes and the sea urchin Diadema antillarum as well as predation by mesofauna on octocoral recruitment through a series of manipulative in situ and ex situ experiments. Exposure to fish and urchin grazing significantly reduced the post-settlement survival of octocoral recruits, while turf-associated mesofauna did not significantly affect recruitment. We also found a positive relationship between octocoral recruitment and the abundance of turf algae, which may reflect the deleterious effect of grazing on both turf algae and octocoral recruits. These data suggest that grazers and predators mediate the bottleneck characteristic of recruitment, primarily through their effect on post-settlement survival. Thus, the declines in the abundance of grazing fishes and urchins throughout the Caribbean may have contributed to the increase in Caribbean octocoral abundance, concurrent with the loss of scleractinians.

Smart Choices Start Here: Engaging Small Food Retailers and Consumers Through Shop Smart Tennessee - Christopher Sneed; Cori Sweet; Betsy Anderson-Steeves; Karen Franck; Jeanmarie Salie; Jennifer Ward; Kristen Johnson (Journal of Nutrition Education and Behavior, 2024)

Soil nitrogen dynamics affected by coffee (coffea arabica) canopy and fertilizer management in coffee-based agroforestry - Syahrul Kurniawan; R Muhammad Yusuf Adi Pujo Nugroho; Reni Ustiatik; Istika Nita; Gabryna Auliya Nugroho; Cahyo Prayogo; Christopher W. N. Anderson (Agroforestry Systems, 2024)
Nutrient management in coffee-based agroforestry systems plays a critical role in soil nitrogen (N) cycling, but has not been well documented. The objective of this study was to evaluate the effect of coffee canopy management and fertilization on soil N dynamics. This study used a randomized complete block design (2 × 3 × 2) with four replications. There were three factors: 1) coffee canopy management (T1: Pruned, T2: Unpruned), 2) fertilizer type (O: Organic, I: Inorganic; M: 50% Organic + 50% Inorganic), and 3) fertilizer dose (D1: low, D2: medium, D3: high). Soil N dynamic indicators (i.e., total N, ammonium (NH 4 + ), nitrate (NO 3 − ), net N-NH 4 + , net N-NO 3 − , soil microbial biomass N) were measured at two soil sampling depths (0–20 cm and 20–40 cm). Results showed that pruning increased soil total N and microbial biomass N (MBN) by 10–56% relative to unpruned coffee trees. In contrast, the unpruned coffee canopy had 15–345% higher NH 4 + , NO 3 − , net N-NH 4 + , net N-NO 3 − , and microbial biomass N concentration than pruned coffee. Mixed fertilizer application increased NO 3 − and net N-NH 4 + accumulation by 5–15% relative to inorganic and organic fertilizers. In addition, medium to high dose fertilization led to a 19–86% higher net N-NO 3 − concentration and microbial biomass N as compared to low dose fertilization. The treatment of no pruning and mixed fertilizer at low to medium doses was the optimal management strategy to maintain soil available N, while pruning combined with organic fertilizer has the potential to improve soil total N and MBN.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Restored Wetland Size and Age Influence Small Mammal Communities in West Virginia, USA - Krista L. Noe; Christopher T. Rota; Mack W. Frantz; James T. Anderson (Wetlands, 2024)
Small mammals are important, albeit often overlooked, fauna in wetland restoration projects. However, it is essential to evaluate factors that influence small mammal community metrics in restored wetlands to maximize wetland restoration effectiveness. Previous studies found that vegetation differed as restored wetlands aged and that wetland age may play a role in the presence of amphibians and birds. Therefore, we assessed whether wetland age influenced small mammals. We also evaluated 17 environmental factors in restored wetlands that could influence small mammal communities in these wetlands. To assess and evaluate the effects of age and environmental factors on the small mammal community, we appraised 14 restored wetlands in West Virginia, USA, in the summers of 2020 and 2021 for small mammal community metrics, specifically relative abundance, diversity, richness, and evenness. We captured six species of small mammals: deer mice ( Peromyscus maniculatus ), white-footed mice ( Peromyscus leucopus ), meadow voles ( Microtus pennsylvanicus ), meadow jumping mice ( Zapus hudsonius ), northern short-tailed shrews ( Blarina brevicauda ), and eastern chipmunks ( Tamias striatus ). We found that the relative abundance of deer mice, white-footed mice, and meadow voles decreased with wetland age. However, both species diversity and evenness increased with wetland age. Wetland size influenced the relative abundance of white-footed mice, meadow jumping mice, and all small mammals combined. Although the relative abundance of white-footed mice and total small mammals decreased with wetland size, the relative abundance of meadow jumping mice increased with wetland size. Wetland managers should consider wetland age and size when designing wetlands to facilitate small mammal communities.

Forging just ecologies: 25 years of urban long-term ecological research collaboration - Morgan Grove; Steward Pickett; Christopher G. Boone; Geoffrey L. Buckley; Pippin Anderson; Fushcia-Ann Hoover; Ariel E. Lugo; Elvia Meléndez-Ackerman; Tischa A. Muñoz-Erickson; Harini Nagendra; L. Kidany Selles (Ambio, 2024)
We ask how environmental justice and urban ecology have influenced one another over the past 25 years in the context of the US Long-Term Ecological Research (LTER) program and Baltimore Ecosystem Study (BES) project. BES began after environmental justice emerged through activism and scholarship in the 1980s but spans a period of increasing awareness among ecologists and environmental practitioners. The work in Baltimore provides a detailed example of how ecological research has been affected by a growing understanding of environmental justice. The shift shows how unjust environmental outcomes emerge and are reinforced over time by systemic discrimination and exclusion. We do not comprehensively review the literature on environmental justice in urban ecology but do present four brief cases from the Caribbean, Africa, and Asia, to illustrate the global relevance of the topic. The example cases demonstrate the necessity for continuous engagement with communities in addressing environmental problem solving.

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Insights from a community of practice: Integrating human rights in fisheries improvement - Elena M. Finkbeiner; Christopher Giordano; Juno Fitzpatrick; Ashley Apel; Cecilia Blasco; Kathryn H. Dalton; Juan Carlos Jerí; Ines Lopez-Ercilla; Gabrielle E. Lout; Chris Madden; Ivan Martinez-Tovar; Pablo Obregon; et al. (Marine Policy, 2024)

Long-Term Climate Impacts on the Phenology of Southern Flounder Spawning Migrations - Joel Anderson; Christopher Steffen; Mark Fisher (Estuaries and Coasts, 2024)

A brief history of the thermal IR-based Two-Source Energy Balance (TSEB) model – diagnosing evapotranspiration from plant to global scales - Martha C. Anderson; William P. Kustas; John M. Norman; George T. Diak; Christopher R. Hain; Feng Gao; Yun Yang; Kyle R. Knipper; Jie Xue; Yang Yang; Wade T. Crow; Thomas R.H. Holmes; et al. (Agricultural and Forest Meteorology, 2024)

National ocean policy in the United States: using framing theory to highlight policy priorities between presidential administrations - Gregory Johnson; Christopher Anderson; Kelly Dunning; Ryan Williamson (Frontiers in Marine Science, 2024)
Coastal and ocean management in the United States is a complex issue requiring an equally complex management policy. Federal policy has historically been carried out in a siloed (sector-by-sector) fashion causing inefficient and bureaucratic management by federal agencies. The Obama administration took a novel approach to coastal and ocean management by signing an executive order that brought together federal agencies and empowered regional stakeholders, creating a first of its kind comprehensive National Ocean Policy. In 2018, former President Donald Trump rescinded the Obama-era policy and enacted his own version of National Ocean Policy that shifted authority to the states and focused on the economic potential of American waters. This research addresses a significant challenge in federal management of a complex natural resource. Here we identify common management strategies between different administrations to provide insights for future attempts at National Ocean Policy. We collect policy documents, press releases, and congressional testimony from high-level stakeholders and identified the most common themes over a 12-year period from 2009-2021. We find three common themes between the administrations even though their policies varied in strategy and scope: 1) the importance of a strong and enduring marine economy, 2) creating a strategic and efficient ocean policy, and 3) devolving authority from the federal government to state and regional decision-makers. We argue that coastal and ocean management via executive order is too easily rescinded to have a lasting impact. These novel findings highlight potential strategies for bipartisan cooperation in future attempts at National Ocean Policy.

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Stakeholder perceptions of coastal environmental stressors in the Florida panhandle - Gregory Johnson; Christopher Anderson; Ryan Williamson; Kelly Dunning (Ocean & Coastal Management, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Surveillance of Infant Formula Shortages Using Special Supplemental Nutrition Program for Women, Infants, and Children Administrative Data - Christopher E. Anderson; Shannon E. Whaley (Journal of Nutrition Education and Behavior, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Globally‐distributed microbial eukaryotes exhibit endemism at deep‐sea hydrothermal vents - Sarah K. Hu; Amy R. Smith; Rika E. Anderson; Sean P. Sylva; Michaela Setzer; Maria Steadmon; Kiana L. Frank; Eric W. Chan; Darlene S. S. Lim; Christopher R. German; John A. Breier; Susan Q. Lang; et al. (Molecular Ecology, 2023)
Single‐celled microbial eukaryotes inhabit deep‐sea hydrothermal vent environments and play critical ecological roles in the vent‐associated microbial food web. 18S rRNA amplicon sequencing of diffuse venting fluids from four geographically‐ and geochemically‐distinct hydrothermal vent fields was applied to investigate community diversity patterns among protistan assemblages. The four vent fields include Axial Seamount at the Juan de Fuca Ridge, Sea Cliff and Apollo at the Gorda Ridge, all in the NE Pacific Ocean, and Piccard and Von Damm at the Mid‐Cayman Rise in the Caribbean Sea. We describe species diversity patterns with respect to hydrothermal vent field and sample type, identify putative vent endemic microbial eukaryotes, and test how vent fluid geochemistry may influence microbial community diversity. At a semi‐global scale, microbial eukaryotic communities at deep‐sea vents were composed of similar proportions of dinoflagellates, ciliates, Rhizaria, and stramenopiles. Individual vent fields supported distinct and highly diverse assemblages of protists that included potentially endemic or novel vent‐associated strains. These findings represent a census of deep‐sea hydrothermal vent protistan communities. Protistan diversity, which is shaped by the hydrothermal vent environment at a local scale, ultimately influences the vent‐associated microbial food web and the broader deep‐sea carbon cycle.

Soil legacy nutrients contribute to the decreasing stoichiometric ratio of N and P loading from the Mississippi River Basin - Zihao Bian; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; Christopher Anderson; Wei‐Jun Cai; Charles S. Hopkinson; Dubravko Justic; Latif Kalin; Steven Lohrenz; Steven McNulty; et al. (Global Change Biology, 2023)
Human‐induced nitrogen–phosphorus (N, P) imbalance in terrestrial ecosystems can lead to disproportionate N and P loading to aquatic ecosystems, subsequently shifting the elemental ratio in estuaries and coastal oceans and impacting both the structure and functioning of aquatic ecosystems. The N:P ratio of nutrient loading to the Gulf of Mexico from the Mississippi River Basin increased before the late 1980s driven by the enhanced usage of N fertilizer over P fertilizer, whereafter the N:P loading ratio started to decrease although the N:P ratio of fertilizer application did not exhibit a similar trend. Here, we hypothesize that different release rates of soil legacy nutrients might contribute to the decreasing N:P loading ratio. Our study used a data‐model integration framework to evaluate N and P dynamics and the potential for long‐term accumulation or release of internal soil nutrient legacy stores to alter the ratio of N and P transported down the rivers. We show that the longer residence time of P in terrestrial ecosystems results in a much slower release of P to coastal oceans than N. If contemporary nutrient sources were reduced or suspended, P loading sustained by soil legacy P would decrease much slower than that of N, causing a decrease in the N and P loading ratio. The longer residence time of P in terrestrial ecosystems and the increasingly important role of soil legacy nutrients as a loading source may explain the decreasing N:P loading ratio in the Mississippi River Basin. Our study underscores a promising prospect for N loading control and the urgency to integrate soil P legacy into sustainable nutrient management strategies for aquatic ecosystem health and water security.

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

Derivation of Naïve Human Embryonic Stem Cells Using a CHK1 Inhibitor - Carol B. Ware; Erica C. Jonlin; Donovan J. Anderson; Christopher Cavanaugh; Jennifer Hesson; Sonia Sidhu; Savannah Cook; Guillermo Villagomez-Olea; Marshall S. Horwitz; Yuliang Wang; Julie Mathieu (Stem Cell Reviews and Reports, 2023)
Embryonic development is a continuum in vivo . Transcriptional analysis can separate established human embryonic stem cells (hESC) into at least four distinct developmental pluripotent stages, two naïve and two primed, early and late relative to the intact epiblast. In this study we primarily show that exposure of frozen human blastocysts to an inhibitor of checkpoint kinase 1 (CHK1) upon thaw greatly enhances establishment of karyotypically normal late naïve hESC cultures. These late naïve cells are plastic and can be toggled back to early naïve and forward to early primed pluripotent stages. The early primed cells are transcriptionally equivalent to the post inner cell mass intermediate (PICMI) stage seen one day following transfer of human blastocysts into in vitro culture and are stable at an earlier stage than conventional primed hESC. Graphical Abstract

Evidence of increasing juvenile white sharks ' ( Carcharodon carcharias ) habitat use at the Northern Channel Islands - Ryan M. Freedman; James M. Anderson; Chris Caldow; Brian Stirling; Patrick Rex; Emily Spurgeon; Steve McCullough; Kady Lyons; Jack May; Connor F. White; Ryan K. Logan; Emily Meese; et al. (Journal of Fish Biology, 2023)
Juvenile white sharks ( Carcharodon carcharias ) typically aggregate along coastal beaches; however, high levels of recruitment and shifting oceanographic conditions may be causing habitat use expansions. Telemetry data indicate increased habitat use at the Northern Channel Islands (California, USA) by juvenile white shark that may be in response to increased population density at aggregation locations, or anomalous oceanographic events that impact habitat use or expand available habitat. Findings illustrate the need for long‐term movement monitoring and understanding drivers of habitat use shifts and expansion to improve ecosystem management.

Increased WIC Benefits for Fruits and Vegetables Increases Food Security and Satisfaction Among California Households with Young Children - Shannon E. Whaley; Christopher E. Anderson; Marisa M. Tsai; Catherine E. Yepez; Lorrene D. Ritchie; Lauren E. Au (Journal of the Academy of Nutrition and Dietetics, 2023)

Use of Interactive Texting Is Associated With Higher Odds of Continued WIC Participation During the COVID-19 Pandemic - Christopher E. Anderson; Shannon E. Whaley (Journal of the Academy of Nutrition and Dietetics, 2023)

An inclusive typology of values for navigating transformations towards a just and sustainable future - Christopher M. Raymond; Christopher B. Anderson; Simone Athayde; Arild Vatn; Ariane M. Amin; Paola Arias-Arévalo; Michael Christie; Mariana Cantú-Fernández; Rachelle K. Gould; Austin Himes; Jasper O. Kenter; Dominic Lenzi; et al. (Current Opinion in Environmental Sustainability, 2023)

Woody Vegetation Indicators vary with time Since Wetland Restoration - Jessica Anne Bryzek; Walter Veselka IV; Christopher T. Rota; James T. Anderson (Wetlands, 2023)

A general approach for evaluating of the coverage, resolution, and representation of streamflow monitoring networks - Christopher P. Konrad; Scott W. Anderson (Environmental Monitoring and Assessment, 2023)
Streamflow monitoring networks provide information for a wide range of public interests in river and streams. A general approach to evaluate monitoring for different interests is developed to support network planning and design. The approach defines three theoretically distinct information metrics (coverage, resolution, and representation) based on the spatial distribution of a variable of interest. Coverage is the fraction of information that a network can provide about a variable when some areas are not monitored. Resolution is the information available from the network relative to the maximum information possible given the number of sites in the network. Representation is the information that a network provides about a benchmark distribution of a variable. Information is defined using Shannon entropy where the spatial discretization of a variable among spatial elements of a landscape or sites in a network indicates the uncertainty in the spatial distribution of the variable. This approach supports the design of networks for monitoring of variables with heterogeneous spatial distributions (“hot spots” and patches) that might otherwise be unmonitored because they occupy insignificant portions of the landscape. Areas where monitoring will maintain or improve the metrics serve as objective priorities for public interests in network design. The approach is demonstrated for the streamflow monitoring network operated by the United States Geological Survey during water year 2020 indicating gaps in the coverage of coastal rivers and the resolution of low flows.

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Midstory removal of encroaching species has minimal impacts on fuels and fire behavior regardless of burn season in a degraded pine-oak mixture - Steven Cabrera; Heather D. Alexander; John L. Willis; Christopher J. Anderson (Forest Ecology and Management, 2023)

Engaging diverse experts in the global science-policy interface: Learning experiences from the process of the IPBES Values Assessment - Katri Mäkinen-Rostedt; Viola Hakkarainen; Max Eriksson; Riley Andrade; Andra Horcea-Milcu; Christopher B. Anderson; Carena J. van Riper; Christopher M. Raymond (Environmental Science & Policy, 2023)

Climate change mitigation in Zimbabwe and links to sustainable development - Dingane Sithole; Caroline Tagwireyi; Tendayi Marowa; Fadzai Muwidzi; Farai Mapanda; Walter Svinurai; Tatenda Gotore; Sekai Ngarize; Anderson Muchawona; Samantha Chigoverah; Gamuchirai Takavingofa; Kudzai Ndidzano; et al. (Environmental Development, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Salinity fluctuations due to urbanization of coastal environments and their potential effect on the genetic divergence of the Gulf killifish (Fundulus grandis) - Brandon Waldo; Katherine Moore; Samuel Bickley; Christopher J. Anderson; Moisés A. Bernal (Environmental Biology of Fishes, 2023)

Loss of microRNA-21 protects against acetaminophen-induced hepatotoxicity in mice - Alexandra M. Huffman; Maryam Syed; Samar Rezq; Christopher D. Anderson; Licy L. Yanes Cardozo; Damian G. Romero (Archives of Toxicology, 2023)

Impact of the 2014–2016 marine heatwave on US and Canada West Coast fisheries: Surprises and lessons from key case studies - Christopher M. Free; Sean C. Anderson; Elizabeth A. Hellmers; Barbara A. Muhling; Michael O. Navarro; Kate Richerson; Lauren A. Rogers; William H. Satterthwaite; Andrew R. Thompson; Jenn M. Burt; Steven D. Gaines; Kristin N. Marshall; et al. (Fish and Fisheries, 2023)
Marine heatwaves are increasingly affecting marine ecosystems, with cascading impacts on coastal economies, communities, and food systems. Studies of heatwaves provide crucial insights into potential ecosystem shifts under future climate change and put fisheries social‐ecological systems through “stress tests” that expose both vulnerabilities and resilience. The 2014–16 Northeast Pacific heatwave was the strongest and longest marine heatwave on record and resulted in profound ecological changes that impacted fisheries, fisheries management, and human livelihoods. Here, we synthesize the impacts of the 2014–2016 marine heatwave on US and Canada West Coast fisheries and extract key lessons for preparing global fisheries science, management, and industries for the future. We set the stage with a brief review of the impacts of the heatwave on marine ecosystems and the first systematic analysis of the economic impacts of these changes on commercial and recreational fisheries. We then examine ten key case studies that provide instructive examples of the complex and surprising challenges that heatwaves pose to fisheries social‐ecological systems. These reveal important insights into improving the resilience of monitoring and management and increasing adaptive capacity to future stressors. Key recommendations include: (1) expanding monitoring to enhance mechanistic understanding, provide early warning signals, and improve predictions of impacts; (2) increasing the flexibility, adaptiveness, and inclusiveness of management where possible; (3) using simulation testing to help guide management decisions; and (4) enhancing the adaptive capacity of fishing communities by promoting engagement, flexibility, experimentation, and failsafes. These advancements are important as global fisheries prepare for a changing ocean.

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

The biology of mammalian multi-copper ferroxidases - Sheridan L. Helman; Jie Zhou; Brie K. Fuqua; Yan Lu; James F. Collins; Huijun Chen; Christopher D. Vulpe; Gregory J. Anderson; David M. Frazer (BioMetals, 2023)

Left Cerebellar Lesions may be Associated with an Increase in Spatial Neglect-like Symptoms - Ryan Verbitsky; Britt Anderson; James Danckert; Sean Dukelow; Christopher L. Striemer (The Cerebellum, 2023)

Actinium and radium fluxes from the seabed in the northeast Pacific Basin - Nathaniel Kemnitz; Douglas E. Hammond; Paul Henderson; Emilie Le Roy; Matthew Charette; Willard Moore; Robert F. Anderson; Martin Q. Fleisher; Anne Leal; Erin Black; Christopher T. Hayes; Jess Adkins; et al. (Marine Chemistry, 2023)

Nitrification rate in dairy cattle urine patches can be inhibited by changing soil bioavailable Cu concentration - Dumsane Themba Matse; Paramsothy Jeyakumar; Peter Bishop; Christopher W.N. Anderson (Environmental Pollution, 2023)

Development of a Benchmark Eddy Flux Evapotranspiration Dataset for Evaluation of Satellite-Driven Evapotranspiration Models Over the CONUS - John M. Volk; Justin Huntington; Forrest S. Melton; Richard Allen; Martha C. Anderson; Joshua B. Fisher; Ayse Kilic; Gabriel Senay; Gregory Halverson; Kyle Knipper; Blake Minor; Christopher Pearson; et al. (Agricultural and Forest Meteorology, 2023)

Reaching Food Retail Customers Through Facebook - Cori Sweet; Jennifer Ward; Jeanmarie Salie; Karen Franck; Elizabeth Anderson Steeves; Christopher T. Sneed; Janie Burney (Journal of Nutrition Education and Behavior, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Distribution and Morphology of Littoraria irrorata in Mesohaline Tidal Marshes Dominated by Juncus roemerianus - Christopher J. Anderson; Cristina Garcia; James S. Cash (Estuaries and Coasts, 2022)

Phenotypic correlates of pelvic spine coloration in the threespine stickleback (Gasterosteus aculeatus): implications for function and evolution - Christopher M. Anderson; Jeffrey S. McKinnon (Behavioral Ecology and Sociobiology, 2022)

Improving the spatiotemporal resolution of remotely sensed ET information for water management through Landsat, Sentinel-2, ECOSTRESS and VIIRS data fusion - Jie Xue; Martha C. Anderson; Feng Gao; Christopher Hain; Kyle R. Knipper; Yun Yang; William P. Kustas; Yang Yang; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; Joseph G. Alfieri; et al. (Irrigation Science, 2022)
Robust information on consumptive water use (evapotranspiration, ET) derived from remote sensing can significantly benefit water decision-making in agriculture, informing irrigation schedules and water management plans over extended regions. To be of optimal utility for operational usage, these remote sensing ET data should be generated at the sub-field spatial resolution and daily-to-weekly timesteps commensurate with the scales of water management activities. However, current methods for field-scale ET retrieval based on thermal infrared (TIR) imaging, a valuable diagnostic of canopy stress and surface moisture status, are limited by the temporal revisit of available medium-resolution (100 m or finer) thermal satellite sensors. This study investigates the efficacy of a data fusion method for combining information from multiple medium-resolution sensors toward generating high spatiotemporal resolution ET products for water management. TIR data from Landsat and ECOSTRESS (both at ~ 100-m native resolution), and VIIRS (375-m native) are sharpened to a common 30-m grid using surface reflectance data from the Harmonized Landsat-Sentinel dataset. Periodic 30-m ET retrievals from these combined thermal data sources are fused with daily retrievals from unsharpened VIIRS to generate daily, 30-m ET image timeseries. The accuracy of this mapping method is tested over several irrigated cropping systems in the Central Valley of California in comparison with flux tower observations, including measurements over irrigated vineyards collected in the GRAPEX campaign. Results demonstrate the operational value added by the augmented TIR sensor suite compared to Landsat alone, in terms of capturing daily ET variability and reduced latency for real-time applications. The method also provides means for incorporating new sources of imaging from future planned thermal missions, further improving our ability to map rapid changes in crop water use at field scales.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Relationship between gene expression networks and muscle contractile physiology differences in Anolis lizards - Luke B. Smith; Christopher V. Anderson; Miyuraj H. Hikkaduwa Withangage; Andrew Koch; Thomas J. Roberts; Andrea L. Liebl (Journal of Comparative Physiology B, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Landscape Controls on Nutrient Stoichiometry Regulate Lake Primary Production at the Margin of the Greenland Ice Sheet - Clay Prater; Joanna E. Bullard; Christopher L. Osburn; Sarah L. Martin; Michael J. Watts; N. John Anderson (Ecosystems, 2022)
Global change is reshaping the physical environment and altering nutrient dynamics across the Arctic. These changes can affect the structure and function of biological communities and influence important climate-related feedbacks (for example, carbon (C) sequestration) in biogeochemical processing hot spots such as lakes. To understand how these ecosystems will respond in the future, this study examined recent (< 10 y) and long-term (1000 y) shifts in autotrophic production across paraglacial environmental gradients in SW Greenland. Contemporary lake temperatures and light levels increased with distance from the ice sheet, along with dissolved organic C (DOC) concentrations and total nitrogen:total phosphorus (TN:TP) ratios. Diatom production measured as biogenic silica accumulation rates (BSiARs) and diatom contribution to microbial communities declined across these gradients, while total production estimated using C accumulation rates and δ 13 C increased, indicating that autochthonous production and C burial are controlled by microbial competition and competitive displacement across physiochemical gradients in the region. Diatom production was generally low across lakes prior to the 1800’s AD but has risen 1.5–3× above background levels starting between 1750 and 1880 AD. These increases predate contemporary regional warming by 115–250 years, and temperature stimulation of primary production was inconsistent with paleorecords for ~ 90% of the last millennium. Instead, primary production appeared to be more strongly related to N and P availability, which differs considerably across the region due to lake landscape position, glacial activity and degree of atmospheric nutrient deposition. These results suggest that biological responses to enhanced nutrient supply could serve as important negative feedbacks to global change.

A Model-Based Approach to Bridging Plasma and Dried Blood Spot Concentration Data for Phase 3 Verubecestat Trials - Marissa F. Dockendorf; David Jaworowicz; Rebecca Humphrey; Melanie Anderson; Sheila Breidinger; Lei Ma; Theresa Taylor; Nicole Dupre; Christopher Jones; Christine Furtek; Bhavna Kantesaria; Kevin P. Bateman; et al. (The AAPS Journal, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Salinity thresholds for understory plants in coastal wetlands - Steven M. Anderson; Emily A. Ury; Paul J. Taillie; Eric A. Ungberg; Christopher E. Moorman; Benjamin Poulter; Marcelo Ardón; Emily S. Bernhardt; Justin P. Wright (Plant Ecology, 2022)

Bioavailable Cu can influence nitrification rate in New Zealand dairy farm soils - Dumsane Themba Matse; Paramsothy Jeyakumar; Peter Bishop; Christopher W. N. Anderson (Journal of Soils and Sediments, 2022)

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Social and Economic Outcomes of Fisheries Certification: Characterizing Pathways of Change in Canned Fish Markets - Christopher M. Anderson; Amber Himes-Cornell; Cristina Pita; Ashleigh Arton; Margaux Favret; Dan Averill; Stephen Stohs; Catherine Sarah Longo (Frontiers in Marine Science, 2021)
The Marine Stewardship Council (MSC) eco-labeling program provides fisheries a pathway to demonstrate their sustainability by undergoing an environmental certification. Like other standard-setters, the MSC’s ‘theory of change’ presumes that markets use this information to select for sustainable products, providing an incentive for producers to improve their practices and become certified. However, the underlying mechanisms which actually work to link market behavior and participation in the program in different contexts have not been systematically identified. We draw on broad MSC field experience to identify processes that have supported the theory of change in individual fisheries. Then, we develop a broadly applicable rapid assessment protocol, relying on a semi-structured interviews of key informants, to gather systematic evidence for key dynamics within the theory of change: the effects of going through MSC certification on market processes, partnerships in the fishery, and governance. In a pilot test of the protocol, we identify important common and idiosyncratic processes in three canned product fisheries: United States west coast albacore tuna, Brittany sardines, and Portuguese sardines. We find that the harvesters and buyers/processors in these fisheries sought certification primarily to expand or maintain their market share, and that certification was synergistic with stakeholder cooperation. The cases demonstrate how our rapid assessment interviews allow program participants to relate their experience in their own words yet facilitate systematic comparison to identify common mechanisms within the theory of change. We propose its wider application to systematically advance our understanding of social and economic processes that drive of eco-label interventions in different geographies and supply chains around the world.

Drought at a coastal wetland affects refuelling and migration strategies of shorebirds - Alexandra M. Anderson; Christian Friis; Cheri L. Gratto-Trevor; Christopher M. Harris; Oliver P. Love; R. I. Guy Morrison; Sean W. J. Prosser; Erica Nol; Paul A. Smith (Oecologia, 2021)
Droughts can affect invertebrate communities in wetlands, which can have bottom-up effects on the condition and survival of top predators. Shorebirds, key predators at coastal wetlands, have experienced widespread population declines and could be negatively affected by droughts. We explored, in detail, the effects of drought on multiple aspects of shorebird stopover and migration ecology by contrasting a year with average wet/dry conditions (2016) with a year with moderate drought (2017) at a major subarctic stopover site on southbound migration. We also examined the effects of drought on shorebird body mass during stopover across 14 years (historical: 1974–1982 and present-day: 2014–2018). For the detailed comparison of two years, in the year with moderate drought we documented lower invertebrate abundance at some sites, higher prey family richness in shorebird faecal samples, lower shorebird refuelling rates, shorter stopover durations for juveniles, and, for most species, a higher probability of making a subsequent stopover in North America after departing the subarctic, compared to the year with average wet/dry conditions. In the 14-year dataset, shorebird body mass tended to be lower in drier years. We show that even short-term, moderate drought conditions can negatively affect shorebird refuelling performance at coastal wetlands, which may carry-over to affect subsequent stopover decisions. Given shorebird population declines and predicted changes in the severity and duration of droughts with climate change, researchers should prioritize a better understanding of how droughts affect shorebird refuelling performance and survival.

Long-term Salinity, Hydrology, and Forested Wetlands Along a Tidal Freshwater Gradient - Seval Celik; Christopher J. Anderson; Latif Kalin; Mehdi Rezaeianzadeh (Estuaries and Coasts, 2021)

Non-random Co-occurrence of Juvenile White Sharks (Carcharodon carcharias) at Seasonal Aggregation Sites in Southern California - James M. Anderson; Alyssa J. Clevenstine; Brian S. Stirling; Echelle S. Burns; Emily N. Meese; Connor F. White; Ryan K. Logan; John O’Sullivan; Patrick T. Rex; Jack May; Kady Lyons; Chuck Winkler; et al. (Frontiers in Marine Science, 2021)
Many terrestrial and aquatic taxa are known to form periodic aggregations, whether across life history or solely during specific life stages, that are generally governed by the availability and distribution of resources. Associations between individuals during such aggregation events are considered random and not driven by social attraction or underlying community structure. White sharks ( Carcharodon carcharias ) have been described as a species that exhibits resource-driven aggregative behaviors across ontogenetic stages and juvenile white sharks are known to form aggregations at specific nursery sites where individuals may remain for extended periods of time in the presence of other individuals. We hypothesized juvenile white sharks form distinct communities during these critical early phases of ontogeny and discuss how a tendency to co-occur across life stages may be seeded by the formation of these communities in early ontogeny. We present results from a series of social network analyses of 86 juvenile white sharks derived from 6 years of passive acoustic telemetry data in southern California, demonstrating the likelihood of association of tagged juvenile white sharks is greater when sharks are of similar size-classes. Individuals in observed networks exhibited behaviors that best approximated fission-fusion dynamics with spatiotemporally unstable group membership. These results provide evidence of possible non-resource driven co-occurrence and community structure in juvenile white sharks during early life stages.

Approaches to regulating recreational fisheries: balancing biology with angler satisfaction - Martin C. Arostegui; Christopher M. Anderson; Rachel F. Benedict; Christopher Dailey; Evan A. Fiorenza; Abby R. Jahn (Reviews in Fish Biology and Fisheries, 2021)

Interannual Nearshore Habitat Use of Young of the Year White Sharks Off Southern California - James M. Anderson; Echelle S. Burns; Emily N. Meese; Thomas J. Farrugia; Brian S. Stirling; Connor F. White; Ryan K. Logan; John O’Sullivan; Chuck Winkler; Christopher G. Lowe (Frontiers in Marine Science, 2021)
Young-of-the-year (YOY) and juvenile-stage white sharks may use southern California nearshore beach habitats more extensively than previously known, within meters of some of the most heavily used beaches in the world. Such knowledge forms a critical component of species management and conservation plans, in addition to public safety and risk mitigation planning. We used data derived from a combination of satellite tag locations (13 animals over 3 years) and passive acoustic monitoring (34 animals over 8 years) to examine the occurrence, relative abundance, and residency patterns of YOY white sharks in southern California waters. Our results suggest that southern California contains spatiotemporally dynamic centers of primary nursery habitat. Tagged YOY white sharks formed loose aggregations at “hotspot” locations that were interannually variable, where individuals exhibited temporal fidelity, higher levels of residency, and spatially restricted movements, with multiple YOY individuals simultaneously displaying this behavior. While models of biotic and abiotic variables suggested relative abundance of tagged sharks may be predicted by sea surface temperature, salinity and productivity (chlorophyll-A), these predictors were not consistent across all years of the study. Thus, novel approaches that incorporate technologies to derive high resolution environmental data, paired with more comprehensive telemetry datasets are therefore required to better understand the extrinsic factors that drive habitat selection and residency patterns in juvenile white sharks.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Wetland Vegetation Response to Groundwater Pumping and Hydrologic Recovery - Megan K. Bartholomew; Christopher J. Anderson; Jacob F. Berkowitz (Wetlands, 2020)
An investigation of wetland vegetation response to groundwater alteration was conducted at the J.B. Starkey Wilderness Park, a large municipal wellfield in the area of west Florida, USA. Decades of historic groundwater withdrawal had created a gradient of impacted wetlands on the wellfield, after which time the groundwater pumping rates were reduced. Nineteen cypress dome wetlands were grouped, based on their hydrologic histories, as either most-altered (least inundation), marginally-altered (intermediate inundation), or least-altered (near-normal inundation). Annual species–level monitoring data were used to evaluate understory plant community response to the hydrologic recovery that resulted from reduced groundwater pumping. Species richness, cover, prevalence index (PI), and species importance percentages were assessed during pre- (2005–2007) and post- (2012–2014) hydrologic recovery periods. The vegetation in marginally- and most-altered wetlands responded to hydrologic recovery with increased species richness and lower PI values (i.e., greater hydrophytic character). However, species importance percentages indicated greater variation in the recovery of most-altered wetlands, where species composition often remained different from least-altered wetlands. Although reductions in groundwater pumping caused sufficient passive hydrologic recovery to elicit a vegetation response, further reductions and/or more time may be needed before the vegetation of some altered wetlands can become comparable to that of least-impacted wetlands.

Feasibility of Igniting Prescribed Fires in Bottomland Hardwood Forests - James S Cash; Christopher J Anderson (Journal of Forestry, 2020)
There is emerging interest in using prescribed fire to manage bottomlands for wildlife habitat, invasive species control, and overall forest function. We evaluated the feasibility of conducting prescribed fires in bottomland hardwood forests in west-central Alabama as part of a broader strategy to control the invasive shrub Chinese privet (Ligustrum sinense). We used 22 small-scale plots (0.04 hectares) in areas with residual slash from privet cutting operations and initiated prescribed fires on each to assess the overall feasibility and the relation of in-stand weather (i.e., microclimate), stand composition, and litter measurements to fire behavior. Overall, prescribed fire ignition was difficult, and only half the trials successfully burned >10 percent of the plot. We found that stand composition was most correlated with percent plot burned, and plots with higher proportions of tree species with flammable leaf traits (e.g., Quercus spp.) tended to burn best. Although further investigation is warranted, managers interested in using prescribed fire for bottomland hardwoods likely face short time windows and limited forest conditions in which fires can be reliably set. Study Implications There is increasing interest in using prescribed fires in bottomland hardwood forests. This exploratory study evaluated whether prescribed fires could be reliably set in bottomlands. Prescribed fires were difficult to establish and tended to be very patchy with fire spread related to tree canopy composition (because of differences in leaf litter flammability) and litter loads. Results suggest that it would be difficult to apply fire on a large scale in bottomland hardwood forests and that small-scale fires could only be set under certain conditions.

The relevance of social imaginaries to understand and manage biological invasions in southern Patagonia - Jessica L. Archibald; Christopher B. Anderson; Mara Dicenta; Catherine Roulier; Kelly Slutz; Erik A. Nielsen (Biological Invasions, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Depth and grazing intensity are the main drivers of subtidal hardground benthic community structure on tropical south Atlantic reefs - Marcelo Checoli Mantelatto; Anderson Eduardo Silva de Oliveira; Carla Menegola; Fernanda Araujo Casares; Joel Christopher Creed (Marine Ecology, 2020)
Marine hardground bottom (subtidal) benthic (sessile) communities (HBBC) are subjected to various biotic, abiotic, and anthropogenic factors that can vary over space and time and interact with one another. To evaluate the main drivers of the structure of HBBC in a large tropical bay in the southwest Atlantic (Ilha Grande Bay, Brazil), a total of 98 HBBC were sampled using visually estimated quadrats. Ten variables (depth, grazing intensity, irradiance, temperature, salinity, dissolved oxygen, nutrients (nitrite, nitrate, and phosphate), and chlorophyll a concentrations) were also measured. A total of 74 main space‐occupying taxon/functional groups were recorded which fell into six major HBBC groups. These were organized by depth/irradiance and grazing intensities which explained part of the HBBC variation: (a) Communities dominated by zoantharians occurred in the shallow, highest irradiance sites; (b) foliose and erect algae were inversely related to depth and grazing intensity; (c) crustose coralline algae dominated at greater depths and/or under higher grazing intensity; (d) zooxanthellate corals were associated with shallower and heterotrophic invertebrates with deeper stations; (e) photosynthetically efficient algae were associated with deeper stations, with more encrusting forms under higher grazing intensities; and (f) multi‐species turf‐forming algae were ubiquitous (did not present association with any of the measured variables). As communities’ components and main structuring factors were similar to those found in coral reefs, these communities represent compatible receptor habitats for poleward escape, migration, and range extension under the present global warming scenario.

Fatty acids elucidate sub-Antarctic stream benthic food web dynamics invaded by the North American beaver (Castor canadensis) - Christopher B. Anderson; Marina Tagliaferro; Aaron Fisk; Amy D. Rosemond; Marisol L. Sanchez; Michael T. Arts (Polar Biology, 2020)

Localization of mercury and gold in cassava (Manihot esculenta Crantz) - Hannah Joy P. Alcantara; Fernando Jativa; Augustine I. Doronila; Christopher W. N. Anderson; Rainer Siegele; Tony G. Spassov; Jose T. Sanchez-Palacios; Berin A. Boughton; Spas D. Kolev (Environmental Science and Pollution Research, 2020)

Predicting evolutionary responses to interspecific interference in the wild - Gregory F. Grether; Jonathan P. Drury; Kenichi W. Okamoto; Shawn McEachin; Christopher N. Anderson (Ecology Letters, 2020)
Many interspecifically territorial species interfere with each other reproductively, and in some cases, aggression towards heterospecifics may be an adaptive response to interspecific mate competition. This hypothesis was recently formalised in an agonistic character displacement (ACD) model which predicts that species should evolve to defend territories against heterospecific rivals above a threshold level of reproductive interference. To test this prediction, we parameterised the model with field estimates of reproductive interference for 32 sympatric damselfly populations and ran evolutionary simulations. Asymmetries in reproductive interference made the outcome inherently unpredictable in some cases, but 80% of the model’s stable outcomes matched levels of heterospecific aggression in the field, significantly exceeding chance expectations. In addition to bolstering the evidence for ACD, this paper introduces a new, predictive approach to testing character displacement theory that, if applied to other systems, could help in resolving long‐standing questions about the importance of character displacement processes in nature.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Risk Management and Analytics in Wildfire Response - Matthew P. Thompson; Yu Wei; David E. Calkin; Christopher D. O’Connor; Christopher J. Dunn; Nathaniel M. Anderson; John S. Hogland (Current Forestry Reports, 2019)
Purpose of Review The objectives of this paper are to briefly review basic risk management and analytics concepts, describe their nexus in relation to wildfire response, demonstrate real-world application of analytics to support response decisions and organizational learning, and outline an analytics strategy for the future. Recent Findings Analytics can improve decision-making and organizational performance across a variety of areas from sports to business to real-time emergency response. A lack of robust descriptive analytics on wildfire incident response effectiveness is a bottleneck for developing operationally relevant and empirically credible predictive and prescriptive analytics to inform and guide strategic response decisions. Capitalizing on technology such as automated resource tracking and machine learning algorithms can help bridge gaps between monitoring, learning, and data-driven decision-making. Summary By investing in better collection, documentation, archiving, and analysis of operational data on response effectiveness, fire management organizations can promote systematic learning and provide a better evidence base to support response decisions. We describe an analytics management framework that can provide structure to help deploy analytics within organizations, and provide real-world examples of advanced fire analytics applied in the USA. To fully capitalize on the potential of analytics, organizations may need to catalyze cultural shifts that cultivate stronger appreciation for data-driven decision processes, and develop informed skeptics that effectively balance both judgment and analysis in decision-making.

Precipitation mediates sap flux sensitivity to evaporative demand in the neotropics - Charlotte Grossiord; Bradley Christoffersen; Aura M. Alonso-Rodríguez; Kristina Anderson-Teixeira; Heidi Asbjornsen; Luiza Maria T. Aparecido; Z. Carter Berry; Christopher Baraloto; Damien Bonal; Isaac Borrego; Benoit Burban; Jeffrey Q. Chambers; et al. (Oecologia, 2019)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Comparing the Slope–Area Threshold for Stream Initiation in Primeval and Managed Forests of Northern Michigan - Christopher J Anderson (Forest Science, 2019)
Forest management and other land uses can alter hydrological pathways and affect stream initiation along draining hillslopes. To evaluate this potential effect, primeval forests at the Huron Mountain Club in northern Michigan were compared to surrounding forest lands historically logged. A total of 59 stream channel heads (19 in primeval forests and 40 in managed forests) were mapped using GPS. Per the slope–area method, channel heads were plotted within a digital elevation model to determine drainage area and local slope, which were used to discern a threshold of channel initiation. A watershed Hydrologic Soil Index (representing the tendency for surface runoff) was also determined and evaluated for its importance for channel formation. Consistent with the slope–area method, a significant relation was detected between drainage area and local slope for both managed (R2 = .29) and primeval forest watersheds (R2 = .56). However, no significant difference in relation was detected between forest types. This was noteworthy because soils mapped in the primeval forests had a significantly higher Hydrologic Soil Index indicating thinner soils more prone to surface runoff. Results suggest that forest management has likely varied throughout the region but has sustained forest drainage densities comparable to primeval forests.

Incentive effect of joint and several liability in fishery cooperatives on regulatory compliance - Manuel Bellanger; Daniel S. Holland; Christopher M. Anderson; Olivier Guyader (Fish and Fisheries, 2019)
Cooperative‐based catch share systems can be implemented such that the members of the same fishery cooperative are jointly and severally liable for not exceeding collectively assigned fishing rights. In practice, this means that a regulator can take away catch privileges from an entire cooperative that overruns its collective quota, effectively creating a penalty much larger than what could be recovered with an individual fine. Fishery cooperatives then typically implement their own internal compliance regime that includes monitoring and penalties. This article first reviews compliance practice in cooperative‐based catch share systems by examining the commonalities and differences in the way compliance regimes are structured (observation and reporting requirements, penalty scheme, internal enforcement authority and indemnification mechanisms) in a number of internal agreements from fishery cooperatives in North America and in Europe. Based on our review of cooperatives and the literature on compliance, we discuss how incentives to comply may be different for an individual fisherman operating in a fishery cooperative where joint and several liability applies as compared to an individual fishing quota baseline situation without fishery cooperative. Our review suggests that, from the regulators’ point of view, joint and several liability can increase the level of compliance for a given enforcement expenditure. However, the regulator cannot rely solely on cooperatives to carry out controls and must ensure that the cooperatives themselves have an interest in setting up an effective monitoring system and will enforce sanctions within the cooperative.

Comparison of vineyard evapotranspiration estimates from surface renewal using measured and modelled energy balance components in the GRAPEX project - Christopher K. Parry; William P. Kustas; Kyle R. Knipper; Martha C. Anderson; Joseph G. Alfieri; John H. Prueger; Andrew J. McElrone (Irrigation Science, 2019)

Crop Water Stress Index of an irrigated vineyard in the Central Valley of California - John H. Prueger; Christopher K. Parry; William P. Kustas; Joseph G. Alfieri; Maria M. Alsina; Héctor Nieto; Tiffany G. Wilson; Lawrence E. Hipps; Martha C. Anderson; Jerry L. Hatfield; Fen Gao; Lynn G. McKee; et al. (Irrigation Science, 2019)

Evapotranspiration estimates derived using thermal-based satellite remote sensing and data fusion for irrigation management in California vineyards - Kyle R. Knipper; William P. Kustas; Martha C. Anderson; Joseph G. Alfieri; John H. Prueger; Christopher R. Hain; Feng Gao; Yun Yang; Lynn G. McKee; Hector Nieto; Lawrence E. Hipps; Maria Mar Alsina; et al. (Irrigation Science, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Applying Public Participation Geographic Information Systems for Coastal Wading Bird Conservation - Cody Cox; Christopher J. Anderson; Wayde C. Morse; John Schelhas (Coastal Management, 2019)

Determining nature’s contributions to achieve the sustainable development goals - Christopher B. Anderson; Cristiana S. Seixas; Olga Barbosa; M. Siobhan Fennessy; Julio Díaz-José; Bernal Herrera-F. (Sustainability Science, 2019)

Evolution and assessment of colour patterns in stream‐resident and anadromous male threespine stickleback Gasterosteus aculeatus from three regions - Adam M. M. Stuckert; Sara Drury; Christopher M. Anderson; Tyler B. T. Bowling; Jeffrey S. Mckinnon (Journal of Fish Biology, 2019)
We compared the colour patterns of free swimming, reproductively active male threespine stickleback Gasterosteus aculeatus of the anadromous and stream ecotypes from three geographically distinct regions. Consistent with the hypothesis of environmentally mediated selection, our results indicate ecologically replicated differences in G. aculeatus coloration between anadromous and stream‐resident populations, and that G. aculeatus probably have the visual acuity to discriminate colour pattern differences between anadromous and stream‐resident fish.

How commercial fishing effort is managed - Christopher M. Anderson; Melissa J. Krigbaum; Martin C. Arostegui; Megan L. Feddern; John Zachary Koehn; Peter T. Kuriyama; Christina Morrisett; Caitlin I. Allen Akselrud; Melanie J. Davis; Courtney Fiamengo; Ava Fuller; Qi Lee; et al. (Fish and Fisheries, 2019)
Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world ( http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.

Soil Conditions Following Hydrologic Restoration in Cypress Dome Wetlands - Megan K. Bartholomew; Christopher J. Anderson; Jacob Berkowitz (Wetlands, 2019)

Growth, Photosynthesis, and Cold Tolerance of Eucalyptus benthamii Planted in the Piedmont of North Carolina - John R Butnor; Kurt H Johnsen; Peter H Anderson; Kevin B Hall; Joshua M Halman; Gary J Hawley; Christopher A Maier; Paul G Schaberg (Forest Science, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Biodiversity monitoring, earth observations and the ecology of scale - Christopher B. Anderson (Ecology Letters, 2018)
Human activity and land‐use change are dramatically altering the sizes, geographical distributions and functioning of biological populations worldwide, with tremendous consequences for human well‐being. Yet our ability to measure, monitor and forecast biodiversity change – crucial to addressing it – remains limited. Biodiversity monitoring systems are being developed to improve this capacity by deriving metrics of change from an array of in situ data (e.g. field plots or species occurrence records) and Earth observations ( EO ; e.g. satellite or airborne imagery). However, there are few ecologically based frameworks for integrating these data into meaningful metrics of biodiversity change. Here, I describe how concepts of pattern and scale in ecology could be used to design such a framework. I review three core topics: the role of scale in measuring and modelling biodiversity patterns with EO , scale‐dependent challenges linking in situ and EO data and opportunities to apply concepts of pattern and scale to EO to improve biodiversity mapping. From this analysis emerges an actionable approach for measuring, monitoring and forecasting biodiversity change, highlighting key opportunities to establish EO as the backbone of global‐scale, science‐driven conservation.

Effects of urbanization on the population structure of freshwater turtles across the United States - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Christopher P. Bloch; Sandra Cooke; Patrick W. Crumrine; Jason Dallas; Alexandra Doran; Jerald J. Dosch; Daniel L. Druckenbrod; Richard D. Durtsche; Danielle Garneau; et al. (Conservation Biology, 2018)
Landscape‐scale alterations that accompany urbanization may negatively affect the population structure of wildlife species such as freshwater turtles. Changes to nesting sites and higher mortality rates due to vehicular collisions and increased predator populations may particularly affect immature turtles and mature female turtles. We hypothesized that the proportions of adult female and immature turtles in a population will negatively correlate with landscape urbanization. As a collaborative effort of the Ecological Research as Education Network (EREN), we sampled freshwater turtle populations in 11 states across the central and eastern United States. Contrary to expectations, we found a significant positive relationship between proportions of mature female painted turtles ( Chrysemys picta ) and urbanization. We did not detect a relationship between urbanization and proportions of immature turtles. Urbanization may alter the thermal environment of nesting sites such that more females are produced as urbanization increases. Our approach of creating a collaborative network of scientists and students at undergraduate institutions proved valuable in terms of testing our hypothesis over a large spatial scale while also allowing students to gain hands‐on experience in conservation science.

Motile Dendritic Cells Sense and Respond to Substrate Geometry - Amy C. Bendell; Nicholas Anderson; Daniel Blumenthal; Edward K. Williamson; Christopher S. Chen; Janis K. Burkhardt; Daniel A. Hammer (Annals of Biomedical Engineering, 2018)

Stable isotope ecology of black rhinos (Diceros bicornis) in Kenya - Thure E. Cerling; Samuel A. Andanje; Francis Gakuya; John M. Kariuki; Linus Kariuki; Jackson W. Kingoo; Cedric Khayale; Isaac Lekolool; Anthony N. Macharia; Christopher R. Anderson; Diego P. Fernandez; Lihai Hu; et al. (Oecologia, 2018)

Correction to: Effect of simulated acid rain on fluorine mobility and the bacterial community of phosphogypsum - Mei Wang; Ya Tang; Christopher W. N. Anderson; Paramsothy Jeyakumar; Jin-yan Yang (Environmental Science and Pollution Research, 2018)

Southern Hemisphere westerly wind influence on southern New Zealand hydrology during the Lateglacial and Holocene - Harris J. Anderson; Christopher M. Moy; Marcus J. Vandergoes; Jonathan E. Nichols; Christina R. Riesselman; Robert Van Hale (Journal of Quaternary Science, 2018)
The strength and latitudinal position of the southern westerly winds (SWW) influence mid‐latitude precipitation and carbon cycling in the Southern Ocean. Despite the important role the westerlies play in the global climate system, past variability is poorly constrained. Here, we present a geochemical record of hydroclimate change from Lake Von in south‐west New Zealand that spans the last 16 000 years. During the Lateglacial and early Holocene, we find stratigraphic and geochemical evidence for three distinct periods of low lake levels that occur during North Atlantic cold events when the Intertropical Convergence Zone is displaced southwards, Southern Ocean upwelling is enhanced and the Antarctic is rapidly warming. We attribute these hydrological changes to southward shifts of the SWW and associated storm tracks that cause arid conditions in southern New Zealand. During the early Holocene, we find evidence for an extended period of low lake levels that are caused by a combination of diminished wind strength, higher air temperatures and reduced seasonality. Finally, we interpret an overall intensification of the SWW after 5500 cal a bp. Our results support the idea that climate mechanisms originating in the high latitudes and the tropics work together to influence the SWW on millennial timescales.

Evaluating the distribution of invasive woody vegetation around riparian corridors in relation to land use - Murat Atasoy; Christopher J. Anderson; Filiz Guneysu Atasoy (Urban Ecosystems, 2018)

Effect of simulated acid rain on fluorine mobility and the bacterial community of phosphogypsum - Mei Wang; Ya Tang; Christopher W. N. Anderson; Paramsothy Jeyakumar; Jinyan Yang (Environmental Science and Pollution Research, 2018)

Sarcocystis myopathy in a patient with HIV-AIDS - Dustin Anderson; Nabeela Nathoo; Jian-Qiang Lu; Kinga T. Kowalewska-Grochowska; Christopher Power (Journal of NeuroVirology, 2018)

Detrended fluctuation analysis and entropy-complexity causality analysis of temperatures in an urbanized mountain stream - Christopher S. Thaxton; W. P. Anderson; Chuanhui Gu; Borko Stosic; Tatijana Stosic (Stochastic Environmental Research and Risk Assessment, 2018)

Establishing habitat‐specific indicator species in Tierra del Fuego with freshwater macroinvertebrates - Christopher B. Anderson; Montana Johnson; María Eugenia Lopez (New Zealand Journal of Marine and Freshwater Research, 2018)
As a tool to understand Tierra del Fuego’s basic ecology and detect changes due to human pressures, this study develops habitat bioindicators. We compared the freshwater benthic macroinvertebrates at 61 study sites in six habitat types: grassland streams, urbanised streams, forested streams, beaver ponds, lakes and peat bog ponds. Forty‐nine taxa were identified; insects were the most diverse group. Beaver pond, lake and grassland stream assemblages were similar, as were those from lakes, grassland streams and peat bog ponds. Fourteen taxa were habitat‐specific. In forests, these included mayfly scrapers ( Andesiops , Meridialaris ) and blackfly filterers ( Gigantodax ). In lakes, two copepod filterers were indicators, and in urban streams, one shredder ( Aphroteniella ) and three collector‐gatherers (springtail, earthworm, aquatic worm). Predators ( Corixa , Aeshna ) were characteristic of peat bog ponds. Beaver ponds had no indicator species. Establishing links between species and ecosystems constitutes the beginning of a broader effort to understand anthropogenic impacts to Fuegian watersheds.

Publishing social science research in Conservation Biology to move beyond biology - Tara L. Teel; Christopher B. Anderson; Mark A. Burgman; Joshua Cinner; Douglas Clark; Rodrigo A. Estévez; Julia P.G. Jones; Tim R. McClanahan; Mark S. Reed; Chris Sandbrook; Freya A.V. St. John (Conservation Biology, 2018)

A neuropathic pain syndrome associated with hantavirus infection - Dustin Anderson; Grayson Beecher; Christopher Power; Lindsay Bridgland; Douglas W. Zochodne (Journal of NeuroVirology, 2017)

Root volume distribution of maturing perennial grasses revealed by correcting for minirhizotron surface effects - Christopher K. Black; Michael D. Masters; David S. LeBauer; Kristina J. Anderson-Teixeira; Evan H. DeLucia (Plant and Soil, 2017)

Urban Land use Affects Resident Fish Communities and Associated Salt Marsh Habitat in Alabama and West Florida, USA - Madeline Wedge; Christopher J. Anderson (Wetlands, 2017)

Temperature–nutrient interactions exacerbate sensitivity to warming in phytoplankton - Mridul K. Thomas; María Aranguren‐Gassis; Colin T. Kremer; Marilyn R. Gould; Krista Anderson; Christopher A. Klausmeier; Elena Litchman (Global Change Biology, 2017)
Temperature and nutrients are fundamental, highly nonlinear drivers of biological processes, but we know little about how they interact to influence growth. This has hampered attempts to model population growth and competition in dynamic environments, which is critical in forecasting species distributions, as well as the diversity and productivity of communities. To address this, we propose a model of population growth that includes a new formulation of the temperature–nutrient interaction and test a novel prediction: that a species’ optimum temperature for growth, T opt , is a saturating function of nutrient concentration. We find strong support for this prediction in experiments with a marine diatom, Thalassiosira pseudonana : T opt decreases by 3–6 °C at low nitrogen and phosphorus concentrations. This interaction implies that species are more vulnerable to hot, low‐nutrient conditions than previous models accounted for. Consequently the interaction dramatically alters species’ range limits in the ocean, projected based on current temperature and nitrate levels as well as those forecast for the future. Ranges are smaller not only than projections based on the individual variables, but also than those using a simpler model of temperature–nutrient interactions. Nutrient deprivation is therefore likely to exacerbate environmental warming's effects on communities.

Soil influences on plant growth, floral density and nectar yield in three cultivars of mānuka ( Leptospermum scoparium ) - Elizabeth M. Nickless; Christopher W. N. Anderson; Georgie Hamilton; Jonathan M. Stephens; Jason Wargent (New Zealand Journal of Botany, 2017)
Honey derived from the nectar of Leptospermum scoparium J.R. et G. Forst. Myrtaceae (mānuka) is a high‐value product and there is considerable potential for economic growth in honey‐growing regions of New Zealand through increased nectar yield from mānuka plantations. Leptospermum scoparium exhibits a significant amount of phenotypic plasticity throughout regions in New Zealand where it has established, although the influences on this plasticity are unknown. When assessing L. scoparium as a nectar source for honey in marginal land areas, the possible effect of soil on nectar chemistry and yield should be considered. We investigated whether phenological patterns of flowering, plant growth, nectar composition and nectar yield were influenced by soil composition. Three different cultivars of L. scoparium were grown on 10 different soils in glasshouse conditions. The soils chosen were representative of the range of New Zealand soils where mānuka is being considered as a commercial crop for the honey industry. ANOVA and general linear models revealed no significant effect of soils on nectar composition or production; however, significant but complex interactions between cultivars and soils influenced plant growth and flowering ( P ≤ 0.05). Accordingly, the overall nectar yield was influenced by cultivar and soil interaction. Measured attributes of the soil such as cation exchange capacity, sulphate, iron, manganese, calcium and chloride were shown to influence the plant parameters assessed. Results allowed modelling of nectar potential against each soil type and established a mānuka soil index to determine the most appropriate soil for each cultivar. The results indicated that potential nectar yield increases will be dependent on cultivars being deployed according to the nature of the soil present. Furthermore, the mānuka cultivars displayed significantly greater growth in response to increased nutrients and some cultivars increased floral density, suggesting potential to improve nectar yield by greater plant growth using targeted fertilisation.

Diffusion Tensor Tractography of the Cerebellar Peduncles in Prematurely Born 7-Year-Old Children - Eilon Shany; Terrie E. Inder; Sharon Goshen; Iris Lee; Jeffrey J. Neil; Christopher D. Smyser; Lex W. Doyle; Peter J. Anderson; Joshua S. Shimony (The Cerebellum, 2017)

Local tidal regime dictates plasticity of expression of locomotor activity rhythms of American horseshoe crabs, Limulus polyphemus - Rebecca L. Anderson; Winsor H. Watson; Christopher C. Chabot (Marine Biology, 2017)

Thermal stratification in small arctic lakes of southwest Greenland affected by water transparency and epilimnetic temperatures - Jasmine E. Saros; Robert M. Northington; Christopher L. Osburn; Benjamin T. Burpee; Nicholas John Anderson (Limnology and Oceanography, 2016)
We assessed which factors control summer epilimnion thickness in arctic lakes of southwest Greenland. A suite of 22 lakes that thermally stratify was measured in the summer of 2013; a sub‐set of eight of the lakes was measured again in 2014, which was a warmer summer than 2013. Regression analysis of the 22 lakes indicated that the 1% attenuation depth for photosynthetically active radiation (PAR) was the strongest single predictor ( R 2 = 0.75) of epilimnion thickness across lakes; the addition of epilimnion temperature to the PAR model explained additional variability ( R 2 = 0.79). The importance of including temperature in the model was apparent in the results of model validation as well as when comparing across years: while the 1% PAR was 0.4–2 m deeper in 2014 compared with 2013, water temperatures were 2–3°C higher, resulting in July epilimnion thicknesses that were equal to or shallower than in 2013. In these lakes with low color dissolved organic carbon (DOC), multiple factors control the 1% PAR, including absorbance at 440 nm ( a 440 ), 380 nm ( a 380 ), and 320 ( a 320 ), chlorophyll a (Chl a ) and DOC concentration. In 2014, when 1% PAR was deeper than in 2013, a 380, Chl a and DOC were lower in six of the eight lakes. Our results reveal that the thermal structure of these arctic lakes is under complex control by air temperatures and factors that affect PAR attenuation, particularly Chl a and DOC quality, suggesting that continued warming in the Arctic will have strong effects on lake stratification.

Heterozygosity, gender, and the growth-defense trade-off in quaking aspen - Christopher T. Cole; Michael T. Stevens; Jon E. Anderson; Richard L. Lindroth (Oecologia, 2016)

Landscape-level impact and habitat factors associated with invasive beaver distribution in Tierra del Fuego - Jonathan J. Henn; Christopher B. Anderson; Guillermo Martínez Pastur (Biological Invasions, 2016)

A New MRI-Based Pediatric Subcortical Segmentation Technique (PSST) - Wai Yen Loh; Alan Connelly; Jeanie L. Y. Cheong; Alicia J. Spittle; Jian Chen; Christopher Adamson; Zohra M. Ahmadzai; Lillian Gabra Fam; Sandra Rees; Katherine J. Lee; Lex W. Doyle; Peter J. Anderson; et al. (Neuroinformatics, 2016)

Evaluating a campus nitrogen budget for Auburn University, Alabama, USA - A. Beau Brodbeck; Judson S. LeCompte; Amanda L. Meder; Matthew C. Ricker; Madeline Wedge; Hanna Schurman; Christopher J. Anderson (Urban Ecosystems, 2015)

Evaluating the Effects of Urban Land Use on the Condition of Resident Salt Marsh Fish - Madeline Wedge; Christopher J. Anderson; Dennis DeVries (Estuaries and Coasts, 2015)

Release of constraints on nest-site selection in burrow-nesting petrels following invasive rat eradication - Rachel T. Buxton; Dean Anderson; Henrik Moller; Christopher J. Jones; Philip O’B. Lyver (Biological Invasions, 2015)

Abundance and phenology patterns of two pond-breeding salamanders determine species interactions in natural populations - Thomas L. Anderson; Daniel J. Hocking; Christopher A. Conner; Julia E. Earl; Elizabeth B. Harper; Michael S. Osbourn; William E. Peterman; Tracy A. G. Rittenhouse; Raymond D. Semlitsch (Oecologia, 2015)

Biogeographically distinct controls on C 3 and C 4 grass distributions: merging community and physiological ecology - Daniel M. Griffith; T. Michael Anderson; Colin P. Osborne; Caroline A. E. Strömberg; Elisabeth J. Forrestel; Christopher J. Still (Global Ecology and Biogeography, 2015)
Aim C 4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C 4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C 3 / C 4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C 3 / C 4 grass distributions. We consider multiple biogeographic regions of N orth A merica using a multisource database of over 40,000 vegetation plots. Location The conterminous U nited S tates of A merica ( USA ). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C 3 and C 4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C 3 ‐ or C 4 ‐dominated states. Transitions between C 3 / C 4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like E astern T emperate F orests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C 3 / C 4 abundance. Main conclusion Local ecological factors modify C 3 / C 4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In E astern T emperate F orests, for example, C 4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.

Stormwater ponds can contain comparable biodiversity to unmanaged wetlands in urban areas - Christopher Hassall; Sarah Anderson (Hydrobiologia, 2015)

Clarifying values, risk perceptions, and attitudes to resolve or avoid social conflicts in invasive species management - Rodrigo A. Estévez; Christopher B. Anderson; J. Cristobal Pizarro; Mark A. Burgman (Conservation Biology, 2015)
Decision makers and researchers recognize the need to effectively confront the social dimensions and conflicts inherent to invasive species research and management. Yet, despite numerous contentious situations that have arisen, no systematic evaluation of the literature has examined the commonalities in the patterns and types of these emergent social issues. Using social and ecological keywords, we reviewed trends in the social dimensions of invasive species research and management and the sources and potential solutions to problems and conflicts that arise around invasive species. We integrated components of cognitive hierarchy theory and risk perceptions theory to provide a conceptual framework to identify, distinguish, and provide understanding of the driving factors underlying disputes associated with invasive species. In the ISI Web of Science database, we found 15,915 peer‐reviewed publications on biological invasions, 124 of which included social dimensions of this phenomenon. Of these 124, 28 studies described specific contentious situations. Social approaches to biological invasions have emerged largely in the last decade and have focused on both environmental social sciences and resource management. Despite being distributed in a range of journals, these 124 articles were concentrated mostly in ecology and conservation‐oriented outlets. We found that conflicts surrounding invasive species arose based largely on differences in value systems and to a lesser extent stakeholder and decision maker's risk perceptions. To confront or avoid such situations, we suggest integrating the plurality of environmental values into invasive species research and management via structured decision making techniques, which enhance effective risk communication that promotes trust and confidence between stakeholders and decision makers. Clarificar los Valores, Percepciones de Riesgo y Actitudes para Resolver o Evitar Conflictos Sociales en el Manejo de Especies Invasoras

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

A Thermodynamic Geography: Night-Time Satellite Imagery as a Proxy Measure of Emergy - Luca Coscieme; Federico M. Pulselli; Simone Bastianoni; Christopher D. Elvidge; Sharolyn Anderson; Paul C. Sutton (Ambio, 2014)

Evaluating the Effects of Land Use on Headwater Wetland Amphibian Assemblages in Coastal Alabama - Diane M. Alix; Christopher J. Anderson; James B. Grand; Craig Guyer (Wetlands, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Perceiving Patagonia: An Assessment of Social Values and Perspectives Regarding Watershed Ecosystem Services and Management in Southern South America - Jean-Paul A. Zagarola; Christopher B. Anderson; James R. Veteto (Environmental Management, 2014)

Comparative tolerance of Pinus radiata and microbial activity to copper and zinc in a soil treated with metal-amended biosolids - Paramsothy Jeyakumar; Paripurnanda Loganathan; Christopher W. N. Anderson; Sivalingam Sivakumaran; Ronald G. McLaren (Environmental Science and Pollution Research, 2014)

GEOTRACES: Changing the Way We Explore Ocean Chemistry - Robert Anderson; Edward Mawji; Gregory Cutter; Christopher Measures; Catherine Jeandel (Oceanography, 2014)

The significance of past interdrainage connectivity for studies of diversity, distribution and movement of freshwater‐limited taxa within a catchment - Cecilia Carrea; Leigh V. Anderson; Dave Craw; Jonathan M. Waters; Christopher P. Burridge (Journal of Biogeography, 2014)
Aim Historical connectivity between drainages may represent an underappreciated contributor to the biodiversity within a catchment. First, we tested whether an isolated population of freshwater‐limited galaxiids represents a contribution by past interdrainage connectivity to this system's biodiversity, rather than reflecting intracatchment dispersal or speciation. Second, we sought to distinguish between possible geomorphic processes that could have allowed any past connectivity. Location The Clutha and adjacent Southland region drainages on the South Island of New Zealand. Methods We estimated the phylogeographical relationships among 466 cytochrome b sequences from ‘roundhead’ Galaxias populations throughout the Southland region and the Clutha drainage, using three different methods. Subsequently, possible geomorphic mechanisms of interdrainage connectivity were examined concurrently with genetic population divergence time estimates obtained by coalescent analysis. Results All samples obtained in the lower Clutha system were genetically attributable to G. gollumoides and reflected at least a third, independent colonization event from Southland involving this species, rather than intradrainage dispersal or speciation by pre‐existing Clutha populations. Geomorphological inferences and divergence time estimates of less than 7 ka are consistent with headwater connections across low divides between the lower Clutha and the Catlins region of Southland, rather than anastomosing of main channels during low sea stands. Main conclusions The observation of at least three interdrainage connectivity events influencing the diversity and distribution of G. gollumoides lineages within the Clutha system highlights the potential significance of these processes as contributors to the magnitude and distribution of biodiversity within catchments.

Thiosulphate-induced mercury accumulation by plants: metal uptake and transformation of mercury fractionation in soil - results from a field study - Jianxu Wang; Xinbin Feng; Christopher W. N. Anderson; Heng Wang; Lulu Wang (Plant and Soil, 2014)

Effect of replacement of fish oil with camelina (Camelina sativa) oil on growth, lipid class and fatty acid composition of farmed juvenile Atlantic cod (Gadus morhua) - Stefanie M. Hixson; Christopher C. Parrish; Derek M. Anderson (Fish Physiology and Biochemistry, 2013)

Degradation and Composition of Polycyclic Aromatic Hydrocarbons (PAHs) Following Oil Exposure in Experimental Salt Marshes - Christopher J. Anderson (Water, Air, & Soil Pollution, 2013)

The introduction of Littorina littorea to British Columbia, Canada: potential impacts and the importance of biotic resistance by native predators - Christopher D. G. Harley; Kathryn M. Anderson; Crystal A.-M. Lebreton; Adrian MacKay; Mónica Ayala-Díaz; Stephanie L. Chong; Laura M. Pond; Julia H. Amerongen Maddison; Boaz H. C. Hung; Samantha L. Iversen; Devina C. M. Wong (Marine Biology, 2013)

Organochlorine Pesticides in Squamate Reptiles from Southern Arizona, USA - Scott M. Weir; Marianne Dobrovolny; Chelsea Torres; Cassie Torres; Matt Goode; Thomas R. Rainwater; Christopher J. Salice; Todd A. Anderson (Bulletin of Environmental Contamination and Toxicology, 2013)

Three-dimensional Quantification of Femoral Head Shape in Controls and Patients with Cam-type Femoroacetabular Impingement - Michael D. Harris; Shawn P. Reese; Christopher L. Peters; Jeffrey A. Weiss; Andrew E. Anderson (Annals of Biomedical Engineering, 2013)

Altered Belowground Carbon Cycling Following Land-Use Change to Perennial Bioenergy Crops - Kristina J. Anderson-Teixeira; Michael D. Masters; Christopher K. Black; Marcelo Zeri; Mir Zaman Hussain; Carl J. Bernacchi; Evan H. DeLucia (Ecosystems, 2013)

Children's daily exposure to polychlorinated biphenyls from dietary supplements containing fish oils - Jeffrey T.F. Ashley; Joshua S. Ward; Christopher S. Anderson; Michael W. Schafer; Linda Zaoudeh; Richard J. Horwitz; David J. Velinsky (Food Additives & Contaminants: Part A, 2013)

Characterization of novel microsatellite loci for Hetaerina americana damselflies, and cross-amplification in other species - Christopher N. Anderson; Gregory F. Grether (Conservation Genetics Resources, 2013)

Quantitative structure–activity relationships for organophosphates binding to acetylcholinesterase - Christopher D. Ruark; C. Eric Hack; Peter J. Robinson; Paul E. Anderson; Jeffery M. Gearhart (Archives of Toxicology, 2013)

Regional climate gradients in precipitation and temperature in response to climate teleconnections in the Greater Everglades ecosystem of South Florida - Christopher S. Moses; William T. Anderson; Colin Saunders; Fred Sklar (Journal of Paleolimnology, 2013)

Characterization of sediment contamination patterns by hydrophobic pesticides to preserve ecosystem functions of drainage lakes - Wei Wang; Laura Delgado-Moreno; Jeremy L. Conkle; Michael Anderson; Christopher Amrhein; Qingfu Ye; Jay Gan (Journal of Soils and Sediments, 2012)

TOMM40 in Cerebral Amyloid Angiopathy Related Intracerebral Hemorrhage: Comparative Genetic Analysis with Alzheimer’s Disease - Valerie Valant; Brendan T. Keenan; Christopher D. Anderson; Joshua M. Shulman; William J. Devan; Alison M. Ayres; Kristin Schwab; Joshua N. Goldstein; Anand Viswanathan; Steven M. Greenberg; David A. Bennett; Philip L. De Jager; et al. (Translational Stroke Research, 2012)

Tight controlled expression and secretion of Lactobacillus brevis SlpA in Lactococcus lactis - Axel Hollmann; Mariano Saviello; Lucrecia Delfederico; Tessália Diniz Luerce Saraiva; Debmalya Barh; Neha Jain; Sandeep Tiwari; Sudha Chandra; Krishnakant Gupta; Vasudeo Zambare; Anil Kumar; Lew Christopher; et al. (Biotechnology Letters, 2012)

A Hydrological Budget (2002–2008) for a Large Subtropical Wetland Ecosystem Indicates Marine Groundwater Discharge Accompanies Diminished Freshwater Flow - Amartya K. Saha; Christopher S. Moses; René M. Price; Victor Engel; Thomas J. Smith; Gordon Anderson (Estuaries and Coasts, 2012)

Characterization of 12 microsatellite loci in the waterfall damselfly (Paraphlebia zoe) for use in population genetic applications - Christopher N. Anderson; Gregory F. Grether; Alex Cordoba-Aguilar (Conservation Genetics Resources, 2012)

Aberrant crypt foci as predictors of colorectal neoplasia on repeat colonoscopy - Joseph C. Anderson; Helen Swede; Tarun Rustagi; Petr Protiva; Devon Pleau; Bruce M. Brenner; Thiruchandurai V. Rajan; Christopher D. Heinen; Joel B. Levine; Daniel W. Rosenberg (Cancer Causes & Control, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Forested Wetland Communities as Indicators of Tidal Influence along the Apalachicola River, Florida, USA - Christopher J. Anderson; B. Graeme Lockaby (Wetlands, 2011)

Research Gaps Related to Forest Management and Stream Sediment in the United States - Christopher J. Anderson; B. Graeme Lockaby (Environmental Management, 2011)

Adaptive responses and latent costs of multigeneration cadmium exposure in parasite resistant and susceptible strains of a freshwater snail - Christopher J. Salice; Todd A. Anderson; G. Roesijadi (Ecotoxicology, 2010)

Beaver invasion alters terrestrial subsidies to subantarctic stream food webs - Christopher B. Anderson; Amy D. Rosemond (Hydrobiologia, 2010)

Rising concentrations of atmospheric CO 2 have increased growth in natural stands of quaking aspen ( Populus tremuloides ) - CHRISTOPHER T. COLE; JON E. ANDERSON; RICHARD L. LINDROTH; DONALD M. WALLER (Global Change Biology, 2010)
As atmospheric CO 2 levels rise, temperate and boreal forests in the Northern Hemisphere are gaining importance as carbon sinks. Quantification of that role, however, has been difficult due to the confounding effects of climate change. Recent large‐scale experiments with quaking aspen ( Populus tremuloides ), a dominant species in many northern forest ecosystems, indicate that elevated CO 2 levels can enhance net primary production. Field studies also reveal that droughts contribute to extensive aspen mortality. To complement this work, we analyzed how the growth of wild aspen clones in Wisconsin has responded to historical shifts in CO 2 and climate, accounting for age, genotype (microsatellite heterozygosity), and other factors. Aspen growth has increased an average of 53% over the past five decades, primarily in response to the 19.2% rise in ambient CO 2 levels. CO 2 ‐induced growth is particularly enhanced during periods of high moisture availability. The analysis accounts for the highly nonlinear changes in growth rate with age, and is unaffected by sex or location sampled. Growth also increases with individual heterozygosity, but this heterozygote advantage has not changed with rising levels of CO 2 or moisture. Thus, increases in future growth predicted from previous large‐scale, common‐garden work are already evident in this abundant and ecologically important tree species. Owing to aspen's role as a foundation species in many North American forest ecosystems, CO 2 ‐stimulated growth is likely to have repercussions for numerous associated species and ecosystem processes.

Using assembly rules to measure the resilience of riparian plant communities to beaver invasion in subantarctic forests - Petra K. Wallem; Christopher B. Anderson; Guillermo Martínez-Pastur; María Vanessa Lencinas (Biological Invasions, 2010)

Involvement of reactive oxygen species in the electrochemical inhibition of barnacle ( Amphibalanus amphitrite ) settlement - Rodolfo E. Pérez-Roa; Marc A. Anderson; Dan Rittschof; Christopher G. Hunt; Daniel R. Noguera (Biofouling, 2009)

Diversity, relative abundance, new locality records and population structure of Antarctic demersal fishes from the northern Scotia Arc islands and Bouvetøya - Christopher D. Jones; M. Eric Anderson; Arcady V. Balushkin; Guy Duhamel; Richard R. Eakin; Joseph T. Eastman; Kristen L. Kuhn; Guillaume Lecointre; Thomas J. Near; Anthony W. North; David L. Stein; Marino Vacchi; et al. (Polar Biology, 2008)

The value of timber quality forests for insect conservation on Tierra del Fuego Island compared to associated non-timber quality stands - María Vanessa Lencinas; Guillermo Martínez Pastur; Christopher B. Anderson; Carlos Busso (Journal of Insect Conservation, 2008)

Spatial and temporal variability of solar ultraviolet exposure of coral assemblages in the Florida Keys: Importance of colored dissolved organic matter - Richard G. Zepp; G. Christopher Shank; Erik Stabenau; Karen W. Patterson; Mike Cyterski; William Fisher; Erich Bartels; Susan L. Anderson (Limnology and Oceanography, 2008)
Solar ultraviolet (UV) radiation can have deleterious effects on coral assemblages in tropical and subtropical marine environments, but little information is available on UV penetration into ocean waters surrounding corals. Here we provide an extensive data set of optical properties in the UV domain (280[en]400 nm) that were obtained during 1998‐2005 at sites located in the Lower and Middle Keys and the Dry Tortugas. Absorption coefficients of the colored component of the dissolved organic carbon (DOC; colored dissolved organic matter [CDOM]) were 6× to 25× larger than particulate absorption coefficients in the UV region, indicating that CDOM controls UV penetration in the inshore coastal waters and reef tract. CDOM absorption coefficients (α CDOM ) and DOC were highly correlated to diffuse attenuation coefficients ( K d ) in the UV spectral region. Measurements using moored sensors showed that UV penetration at the reef tract in the Lower Keys varies significantly from day to day and diurnally. The diurnal variations were linked to tidal currents that transport CDOM over the reef tract. Summertime stratification of Case 1 bluewaters near the reef tract during periods of low wind resulted in higher temperatures and UV penetration than that observed during well‐mixed conditions. This result suggests that higher UV exposure accompanying ocean warming during low‐wind doldrums conditions significantly contributes to coral bleaching. Modeling results indicate that changes in underwater sunlight attenuation over the coral reefs can affect UV‐induced deoxyribonucleic acid (DNA) damage and inhibition of coral photosynthesis much more strongly than changes in the stratospheric ozone layer.

An in situ mesocosm method for quantifying nitrogen cycling rates in oligotrophic wetlands using 15N tracer techniques - Jeffrey R. Wozniak; Daniel L. Childers; William T. Anderson; David T. Rudnick; Christopher J. Madden (Wetlands, 2008)

Geochemistry of iron in the Salton Sea, California - Jason P. de Koff; Michael A. Anderson; Christopher Amrhein (Hydrobiologia, 2008)

The complete nucleotide sequence of the cassava (Manihot esculenta) chloroplast genome and the evolution of atpF in Malpighiales: RNA editing and multiple losses of a group II intron - Henry Daniell; Kenneth J. Wurdack; Anderson Kanagaraj; Seung-Bum Lee; Christopher Saski; Robert K. Jansen (Theoretical and Applied Genetics, 2008)

Ecosystem engineering by invasive exotic beavers reduces in-stream diversity and enhances ecosystem function in Cape Horn, Chile - Christopher B. Anderson; Amy D. Rosemond (Oecologia, 2007)

Erratum to: Sediment, carbon, and nutrient accumulations at two 10-year-old created riverine marshes - Christopher J. Anderson; William J. Mitsch (Wetlands, 2007)

Relative Importance of Wetland type Versus Anthropogenic Activities in Determining Site Invasibility - Gary Ervin; Melissa Smothers; Christopher Holly; Cori Anderson; Jeffrey Linville (Biological Invasions, 2006)

Sediment, carbon, and nutrient accumulation at two 10-year-old created riverine marshes - Christopher J. Anderson; William J. Mitsch (Wetlands, 2006)

Exotic Vertebrate Fauna in the Remote and Pristine Sub-Antarctic Cape Horn Archipelago, Chile - Christopher B. Anderson; Ricardo Rozzi; Juan C. Torres-Mura; Steven M. Mcgehee; Margaret F. Sherriffs; Elke Schüttler; Amy D. Rosemond (Biodiversity and Conservation, 2006)

Effect of Thioligands on Plant-Hg Accumulation and Volatilisation from Mercury-contaminated Mine Tailings - Fabio N. Moreno; Christopher W. N. Anderson; Robert B. Stewart; Brett H. Robinson; Roberto Nomura; Mory Ghomshei; John A Meech (Plant and Soil, 2005)

Mechanisms of Haem and Non-Haem Iron Absorption: Lessons from Inherited Disorders of Iron Metabolism - Gregory J Anderson; David M Frazer; Andrew T McKie; Christopher D Vulpe; Ann Smith (BioMetals, 2005)

Estimated contribution of Atlantic Coastal loggerhead turtle nesting populations to offshore feeding aggregations - Mark A. Roberts; Christopher J. Anderson; Bruce Stender; Al Segars; J. David Whittaker; James M. Grady; Joseph M. Quattro (Conservation Genetics, 2005)

Mulching effects on the seasonally flooded zone of west-central Florida, USA wetlands - Christopher J. Anderson; Bruce C. Cowell (Wetlands, 2004)

High-resolution comparative mapping of pig Chromosome 4, emphasizing the FAT1 region - Maria Moller; Frida Berg; Juliette Riquet; Daniel Pomp; Alan Archibald; Susan Anderson; Katia Feve; Yuandan Zhang; Max Rothschild; Denis Milan; Leif Andersson; Christopher K. Tuggle (Mammalian Genome, 2004)

Diversity, floristic and structural patterns of cerrado vegetation in Central Brazil - Jeanine Maria Felfili; Manoel Cláudio da Silva Júnior; Anderson Cássio Sevilha; Christopher William Fagg; Bruno Machado Teles Walter; Paulo Ernane Nogueira; Alba Valéria Rezende (Plant Ecology, 2004)

In vivo videomicroscopy reveals differential effects of the vascular-targeting agent ZD6126 and the anti-angiogenic agent ZD6474 on vascular function in a liver metastasis model - Hemanth Varghese; Lisa Mackenzie; Alan Groom; Christopher Ellis; Anderson Ryan; Ian Macdonald; Ann Chambers (Angiogenesis, 2004)

Administration of the D1-like dopamine receptor antagonist SCH-23390 into the medial nucleus accumbens shell attenuates cocaine priming-induced reinstatement of drug-seeking behavior in rats - Sharon M. Anderson; Ausaf A. Bari; R. Christopher Pierce (Psychopharmacology, 2003)

Preliminary Assessment of Perchlorate in Ecological Receptors at the Longhorn Army Ammunition Plant (LHAAP), Karnack, Texas - Philip N. Smith; Christopher W. Theodorakis; Todd A. Anderson; Ronald J. Kendall (Ecotoxicology, 2001)

Analgesia induced by chronic nicotine infusion in rats - Carstens E.; Kenton Anderson; Christopher Simons; Mirela Carstens; Steven Jinks (Psychopharmacology, 2001)

Association of mammographically defined percent breast density with epidemiologic risk factors for breast cancer (United States) - Celine M. Vachon; Christopher C. Kuni; Kristin Anderson; V. Elving Anderson; Thomas A. Sellers (Cancer Causes & Control, 2000)

Ca 2+ /Calmodulin-dependent protein kinase IV and calcium signaling - Kristin A Anderson; Christopher D Kane (BioMetals, 1998)

Detection of Single Nucleotide Variations in Viral RNA Populations by Primer Extension - Christopher L. Blanchard; Beau J. Anderson (Plant Molecular Biology Reporter, 1998)

Epidemiology of communicable disease in small populations - Christopher J. Rhodes; A. R. Butler; Roy M. Anderson (Journal of Molecular Medicine, 1998)

Electrophysiologic changes in peripheral nerve following repeated exposure to organophosphorus agents - Rebecca J. Anderson; Christopher B. Dunham (Archives of Toxicology, 1985)